Optical laminate and method for producing same

By using a liquid crystal layer with low puncture elastic modulus in the optical Raman sheet, the cracks and damage problems caused by inconsistent separation speed of the substrate layer are solved, and stable separation of the substrate layer and high-quality production of the optical Raman sheet are achieved.

JP7660650B2Active Publication Date: 2025-04-11SUMITOMO CHEM CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023205118
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2025-04-11
Estimated Expiration
2040-03-09

AI Technical Summary

Technical Problem

When manufacturing optical Raman sheets, the separation speed of the substrate layer is too fast or too slow may lead to cracks in the Raman layer or damage to the substrate layer, affecting the quality of the optical Raman sheet.

Method used

An optical Raman sheet with a low puncture elastic modulus is adopted, including a liquid crystal layer between the optical film, the pressure-sensitive adhesive layer and the Raman layer. By adjusting the hardening degree and layer thickness of the liquid crystal layer, it ensures that the Raman layer can smoothly follow the separation of the substrate layer during the separation process and avoid cracks and damage.

Benefits of technology

The stable separation of the substrate layer is achieved. Regardless of the separation speed, the damage of the Raman layer and the substrate layer can be avoided, and the production reliability and quality of optical Raman sheets are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660650000007
    Figure 0007660650000007
  • Figure 0007660650000008
    Figure 0007660650000008
  • Figure 0007660650000009
    Figure 0007660650000009
Patent Text Reader

Abstract

To provide an optical laminate and a manufacturing method for the same, with which, when separating a base material layer during manufacture of an optical laminate, it is easy to carry out the separation of the base material layer irrespective of the separation rate of the base material layer.SOLUTION: The optical laminate includes a phase difference layer containing layer that includes an optical film, an adhesive layer and a phase difference layer (X) in the order stated. The phase difference layer (X) is arranged at a farthest position from the adhesive layer in the phase difference layer containing layer, includes a liquid crystal layer which is the cured layer of a polymerizable liquid crystal compound, and its piercing elastic modulus E(X) is 15 g / mm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical laminate and a method for producing the same. [Background technology]

[0002] Organic EL display devices using organic light-emitting diodes (OLEDs) are not only lighter and thinner than liquid crystal display devices, but also have the advantage of being able to achieve high image quality with a wide viewing angle, fast response speed, and high contrast, and are therefore used in a variety of fields, including smartphones, televisions, and digital cameras. It is known that in organic EL display devices, the anti-reflection performance is improved by using circular polarizers, etc., in order to suppress the deterioration of visibility caused by the reflection of external light.

[0003] For example, Patent Documents 1 and 2 disclose an optical laminate having an anti-reflection function applied to an image display panel such as an organic EL display device, in which a polarizing plate including a linear polarizing layer is provided with two retardation layers formed of a liquid crystal compound and laminated with each other via an adhesive layer. Patent Document 2 describes that two laminates each having an alignment film and a retardation layer formed on a base layer are prepared, the retardation layer sides of the two laminates are bonded together with an adhesive layer, one base layer is peeled off, a polarizing plate is bonded with the adhesive layer, and then the other base layer is peeled off to produce an optical laminate. Patent Document 3 discloses that a retardation layer such as a λ / 4 plate formed using a liquid crystal compound is provided on a transparent support (base layer), and the retardation layer provided on the transparent support is transferred to a polarizing plate to produce a circular polarizing plate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-102286 A [Patent Document 2] JP 2015-40953 A [Patent Document 3] JP 2015-187717 A Summary of the Invention [Problem to be solved by the invention]

[0005] In the retardation layer formed by using a liquid crystal compound as described in Patent Documents 1 to 3, a laminate in which a retardation layer is formed on a base layer is prepared, and a circular polarizing plate is manufactured by using this laminate. In this case, the retardation layer side of the laminate is bonded to a polarizing plate, and then the base layer of the laminate is separated to transfer the retardation layer to the polarizing plate, thereby manufacturing a circular polarizing plate.

[0006] However, when the base layer is separated after laminating the polarizing plate and the retardation layer, problems such as cracks occurring in the retardation layer or breakage of the base layer can occur depending on the speed at which the base layer is separated (separation speed).

[0007] The present invention provides an optical laminate and a method for producing the same, which facilitates favorable separation of a base layer regardless of the separation speed of the base layer when the base layer is separated during production of the optical laminate, etc. [Means for solving the problem]

[0008] The present invention provides the following optical laminate and manufacturing method. [1] An optical laminate including, in this order, an optical film, a pressure-sensitive adhesive layer, and a retardation layer-containing layer including a retardation layer (X), The retardation layer (X) is The retardation layer-containing layer is disposed at a position farthest from the pressure-sensitive adhesive layer, A liquid crystal layer (X) which is a cured layer of a polymerizable liquid crystal compound; and An optical laminate having a puncture elastic modulus E(X) of 15 g / mm or less. [2] The retardation layer (X) is a laminate of a liquid crystal layer (X) and an alignment layer (X), The optical laminate according to [1], wherein the alignment layer (X) is provided on the side of the liquid crystal layer (X) opposite to the pressure-sensitive adhesive layer side. [3] Further, the retardation layer (X) has a base layer (X) on the opposite side to the pressure-sensitive adhesive layer side, The optical laminate according to [1] or [2], wherein the base layer (X) is separably provided between the base layer (X) and the liquid crystal layer (X). [4] The retardation layer-containing layer includes, in order from the pressure-sensitive adhesive layer side, a first retardation layer, an attachment layer, and a second retardation layer, The first retardation layer includes a first liquid crystal layer which is a cured layer of a polymerizable liquid crystal compound, The optical laminate according to any one of [1] to [3], wherein the second retardation layer is the retardation layer (X). [5] The optical laminate according to any one of [4], wherein the first retardation layer is a laminate of the first liquid crystal layer and a first alignment layer. [6] The optical laminate according to [4] or [5], wherein the first retardation layer has a puncture elastic modulus E1 of 15 g / mm or less. [7] The optical laminate according to any one of [4] to [6], wherein the attachment layer is a cured adhesive layer. [8] The optical laminate according to any one of [1] to [3], wherein the retardation layer-containing layer is the retardation layer (X). [9] The pressure-sensitive adhesive layer has a storage modulus of 3.0 × 10 6 N / m 2 The optical laminate according to any one of [1] to [8], which is:

[10] The pressure-sensitive adhesive layer has a storage modulus of 6.0 × 10 5 N / m 2 The optical laminate according to any one of [1] to [9], which is:

[11] The optical laminate according to any one of [1] to

[10] , wherein the optical film includes a polarizing plate having a protective layer provided on one or both sides of a linear polarizing layer.

[12] A method for producing an optical laminate comprising an optical film, a pressure-sensitive adhesive layer, and a retardation layer-containing layer including a retardation layer (X) in this order, comprising: A step of preparing a substrate-layer-attached retardation layer (X) having a substrate layer (X) and the retardation layer (X); A step of preparing a laminate having the optical film, the pressure-sensitive adhesive layer, the retardation layer-containing layer, and the base layer (X) in this order, using the optical film, the pressure-sensitive adhesive layer, and the base layer-attached retardation layer (X); and peeling the base layer (X) from the laminate, The retardation layer (X) is The retardation layer-containing layer is disposed at a position farthest from the pressure-sensitive adhesive layer, A liquid crystal layer (X) formed by polymerizing a polymerizable liquid crystal compound on the base layer (X), and A method for producing an optical laminate, the method comprising the steps of: (a) forming a laminate having a puncture elastic modulus E(X) of 15 g / mm or less;

[13] The retardation layer-containing layer includes, in order from the pressure-sensitive adhesive layer side, a first retardation layer, an attachment layer, and a second retardation layer, the first retardation layer includes a first liquid crystal layer formed by polymerizing a polymerizable liquid crystal compound on a first base layer, The method for producing an optical laminate according to

[12] , wherein the second retardation layer is the retardation layer (X).

[14] The step of preparing the laminate comprises: A step of preparing a base layer-attached first retardation layer having the first base layer and the first retardation layer; The first retardation layer side of the base layer-attached first retardation layer and the base layer-attached retardation layer (X) a step of laminating the retardation layer (X) side via the lamination layer; A step of separating the first base layer after the step of bonding via the bonding layer; and bonding the optical film to an exposed surface exposed by separating the first base layer via the pressure-sensitive adhesive layer.

[15] The step of preparing the laminate comprises: A step of preparing a base layer-attached first retardation layer having the first base layer and the first retardation layer; a step of bonding the optical film and the first retardation layer side of the base layer-attached first retardation layer via a pressure-sensitive adhesive layer; a step of separating the first base layer after the step of bonding via the pressure-sensitive adhesive layer; and bonding an exposed surface exposed by separating the first base material layer and a side of the retardation layer (X) of the base material layer-attached retardation layer (X) via the bonding layer.

[16] The method for producing an optical laminate according to

[15] , wherein the first retardation layer has a puncture elastic modulus E1 of 15 g / mm or less.

[17] The method for producing an optical laminate according to any one of

[14] to

[16] , wherein the first retardation layer with a base layer has a first alignment layer between the first base layer and the first liquid crystal layer.

[18] The retardation layer-containing layer is the retardation layer (X), The step of preparing the laminate includes: and bonding the optical film and the retardation layer (X) side of the base layer-attached retardation layer (X) via the pressure-sensitive adhesive layer.

[19] The method for producing an optical laminate according to any one of

[12] to

[18] , wherein the retardation layer (X) with a base layer has an alignment layer between the base layer (X) and the liquid crystal layer (X). Effect of the Invention

[0009] According to the present invention, when the base layer is separated during the production of an optical laminate, the base layer can be easily and satisfactorily separated regardless of the separation speed of the base layer. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a modified example of the optical laminate of the first embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate having a base layer of the present invention. [Figure 4]FIG. 2 is a schematic cross-sectional view showing an example of a modified example of an optical laminate having a base layer of the present invention. [Diagram 5] FIG. 2 is a schematic cross-sectional view showing an example of a manufacturing process for the optical laminate according to the first embodiment of the present invention. [Figure 6] 4 is a schematic cross-sectional view showing another example of the manufacturing process of the optical laminate according to the first embodiment of the present invention. FIG. [Figure 7] FIG. 4 is a schematic cross-sectional view showing an example of an optical laminate according to a second embodiment of the present invention. [Figure 8] FIG. 1 is a schematic cross-sectional view showing an example of an optical laminate having a base layer of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, preferred embodiments of the optical laminate and the method for producing the same of the present invention will be described with reference to the drawings.

[0012] <Optical laminate and method for producing same> The optical laminate of this embodiment includes an optical film, a pressure-sensitive adhesive layer, and a retardation layer-containing layer including a retardation layer (X) in this order. The retardation layer (X) is disposed at the position farthest from the pressure-sensitive adhesive layer in the retardation layer-containing layer, includes a liquid crystal layer which is a cured layer of a polymerizable liquid crystal compound, and has a puncture modulus E(X) of 15 g / mm or less. The optical laminate may further include a substrate layer (X) on the opposite side of the retardation layer-containing layer from the pressure-sensitive adhesive layer.

[0013] The retardation layer-containing layer may contain a retardation layer (X), and may be, for example, the retardation layer (X) itself, or may contain a retardation layer other than the retardation layer (X) and the retardation layer (X). The other retardation layer contained in the retardation layer is preferably one layer, may be two or more layers, and usually is 5 layers or less, and may be 3 layers or less. When the retardation layer-containing layer contains other retardation layers, the retardation layer-containing layer is preferably a laminate containing the retardation layer (X), one or more other retardation layers, and one or more lamination layers for laminating the retardation layer (X) and the other retardation layers or the other retardation layers to each other. When the retardation layer-containing layer contains other retardation layers, the retardation layer (X) is disposed at a position farthest from the pressure-sensitive adhesive layer in the lamination direction of the optical laminate, and the other retardation layers are disposed between the pressure-sensitive adhesive layer and the retardation layer (X) of the optical laminate. The retardation layer-containing layer is preferably a laminate of the retardation layer (X) and another retardation layer (first embodiment described later), or is the retardation layer (X) itself (second embodiment described later).

[0014] In the above optical laminate, the puncture elastic modulus E(X) of the retardation layer (X) is in the above range. It is considered that the smaller the puncture elastic modulus E(X) of the retardation layer (X), the softer the retardation layer (X). As described later, the optical laminate can be obtained by separating the base layer (X). When the puncture elastic modulus E(X) of the retardation layer (X) is small, the retardation layer (X) is more likely to follow the movement of peeling off the base layer (X), and therefore it is considered that the base layer (X) is easily separated regardless of the separation speed of the base layer (X).

[0015] The method for producing an optical laminate of the present embodiment is the method for producing the optical laminate described above, A step of preparing a substrate layer-attached retardation layer (X) having a substrate layer (X) and a retardation layer (X); A step of preparing a laminate having an optical film, a pressure-sensitive adhesive layer, a retardation layer-containing layer, and a base layer (X) in this order, using an optical film, a pressure-sensitive adhesive layer, and a base layer-attached retardation layer (X); and peeling the base layer (X) from the laminate.

[0016] Hereinafter, the optical laminate and its manufacturing method will be described in detail with specific examples. In the optical laminate and its manufacturing method of the first embodiment, the retardation layer-containing layer is a retardation laminate of a first retardation layer and a second retardation layer, the second retardation layer corresponds to the retardation layer (X), and the base layer-attached retardation layer (X) corresponds to the base layer-attached second retardation layer. In the optical laminate and its manufacturing method of the second embodiment, the retardation layer-containing layer is the retardation layer (X) itself.

[0017] (Optical laminate of the first embodiment) 1 to 4 are schematic cross-sectional views showing an example of an optical laminate of this embodiment (first embodiment). As shown in FIGS. 1 to 4, the optical laminates 1a, 1b, 1c, and 1d of this embodiment (hereinafter, these may be collectively referred to as "optical laminate 1") include an optical film 40, a pressure-sensitive adhesive layer 31, a first retardation layer 10, an attachment layer 32, and a second retardation layer 20 (retardation layer (X)) in this order. The first retardation layer 10, the attachment layer 32, and the second retardation layer 20 constitute a retardation layer-containing layer. The first retardation layer 10 includes a first liquid crystal layer 12 which is a cured layer of a polymerizable liquid crystal compound. The second retardation layer 20 includes a second liquid crystal layer 22 (liquid crystal layer (X)) which is a cured layer of a polymerizable liquid crystal compound. The puncture elastic modulus E2 of the second retardation layer 20 (puncture elastic modulus E(X) ) is 15g / mm or less.

[0018] 3 and 4, the optical laminate 1 may have a second base layer 25 (base layer (X)) on the side opposite to the bonding layer 32 side of the second retardation layer 20. The second base layer 25 is preferably provided separably between the second base layer 25 and the second liquid crystal layer 22 included in the second retardation layer 20.

[0019] The term "separable" between the second substrate layer 25 and the second liquid crystal layer 22 means that the second substrate layer 25 is peelable from the second liquid crystal layer 22, or that the second substrate layer 25 is peelable from the second substrate layer 21 when the second alignment layer 21 is present between the second substrate layer 25 and the second liquid crystal layer 22, or that the second alignment layer 21 is peelable from the second liquid crystal layer 22. Therefore, when the second substrate layer 25 is peelable from the second alignment layer 21, the second alignment layer 21 remains on the second liquid crystal layer 22 when the second substrate layer 25 is separated from the optical laminate 1c, 1d (FIGS. 3 and 4) (FIGS. 1 and 2). When the second alignment layer 21 is peelable from the second liquid crystal layer 22, the second substrate layer 25 is peeled off together with the second substrate layer 25 when the second substrate layer 25 is separated from the optical laminate 1a.

[0020] The first retardation layer 10 may be the first liquid crystal layer 12 itself, which is a cured layer of a polymerizable liquid crystal compound, or may be a laminate of the first liquid crystal layer 12 and the first alignment layer 11. When the first retardation layer 10 has the first alignment layer 11, the first alignment layer 11 may be provided on the side opposite to the second retardation layer 20 side of the first liquid crystal layer 12 (FIG. 1), or may be provided on the second retardation layer 20 side of the first liquid crystal layer 12 (FIG. 2).

[0021] The puncture elastic modulus E1 of the first retardation layer 10 is not particularly limited, and may be, for example, 50 g / mm or less, 40 g / mm or less, 30 g / mm or less, 20 g / mm or less, preferably 15 g / mm or less, 12 g / mm or less, 10 g / mm or less, or 9 g / mm or less. The puncture elastic modulus E1 is usually 3 g / mm or more, 5 g / mm or more, 7 g / mm or more, or 10 g / mm or more. The puncture elastic modulus E1 is a value at a temperature of 23° C. and a relative humidity of 50%, and can be measured according to the procedure of the puncture elastic modulus measurement method described in the examples below. When the first retardation layer 10 is a laminate of the first liquid crystal layer 12 and the first alignment layer 11, the puncture elastic modulus E1 of the first retardation layer 10 is measured by piercing the first alignment layer 11 side with a needle. In the first retardation layer 10, the temperature dependency of the puncture elastic modulus E1 is not observed in the range of 23 to 80°C.

[0022] In the optical laminates 1b and 1d (FIGS. 2 and 4), the puncture elastic modulus E1 of the first retardation layer 10 is preferably 15 g / mm or less, may be 12 g / mm or less, may be 10 g / mm or less, or may be 9 g / mm or less. The puncture elastic modulus E2 is usually 3 g / mm or more, may be 5 g / mm or more, or may be 7 g / mm or more.

[0023] The puncture modulus E1 of the first retardation layer 10 can be adjusted by, for example, the type and polymerization degree (hardening degree) of the polymerizable liquid crystal compound constituting the first liquid crystal layer 12, the type and amount of additives such as a polymerization initiator, a reactive additive, a leveling agent, a polymerization inhibitor, and a crosslinking agent contained in the first liquid crystal layer 12, the type and polymerization degree (hardening degree) of the polymerizable compound in the hardening resin composition constituting the first alignment layer 11, the thickness of the first retardation layer 10, and the like. Usually, the value of the puncture modulus E1 increases as the polymerization degree (hardening degree) increases. In addition, the puncture modulus E1 of the first retardation layer 10 can also be adjusted by the crosslink density of the first liquid crystal layer 12 and the crosslink density of the first alignment layer 11. For example, in order to increase the crosslink density of the first liquid crystal layer 12, a polyfunctional polymerizable liquid crystal compound having three or more polymerizable groups in the molecule is used as the polymerizable liquid crystal compound for forming the first liquid crystal layer 12. Just use things.

[0024] In order to set the puncture modulus E1 of the first retardation layer 10 within a predetermined range, for example, a preliminary experiment is performed in which the degree of polymerization (hardening degree) of the polymerizable liquid crystal compound and the degree of polymerization (hardening degree) of the first alignment layer 11 are controlled, and the desired puncture modulus E1 can be set. As such a preliminary experiment, for example, when controlling the degree of polymerization of the first liquid crystal layer, it can be performed as follows. First, a coating layer of a liquid crystal layer forming composition containing a polymerizable liquid crystal compound is provided on a first base layer (a first alignment layer may be provided), and the coating layer is irradiated with ultraviolet light or the like to form a first liquid crystal layer on the first base layer. The ratio (relative value) of the amount of polymerizable groups of the polymerizable liquid crystal compound contained in the coating layer to the amount of polymerizable groups of the polymerizable liquid crystal compound contained in the first liquid crystal layer is measured by infrared absorption (IR) spectrum measurement or the like to determine the degree of polymerization (hardening degree). The puncture modulus E1 of the first retardation layer including the first liquid crystal layer obtained at this time is measured, and the degree of polymerization and the puncture modulus E1 determined above are related to each other. This procedure is carried out by changing the type of polymerizable liquid crystal compound, the amount of irradiation of ultraviolet light, etc. In this way, the correlation between the degree of polymerization and the puncture elastic modulus E1 can be obtained, and the degree of polymerization for obtaining a desired puncture elastic modulus E1 can be determined.

[0025] The thickness of the first retardation layer 10 is preferably 1.0 μm or more, more preferably 1.5 μm or more, may be 1.7 μm or more, or may be 2.0 μm or more. The thickness of the first retardation layer 10 is usually 8 μm or less, may be 5 μm or less, or may be 3 μm or less.

[0026] The second retardation layer 20 may be the second liquid crystal layer 22 itself, which is a cured layer of a polymerizable liquid crystal compound, or may be a laminate of the second liquid crystal layer 22 and the second alignment layer 21. When the second retardation layer 20 has the second alignment layer 21, the second alignment layer 21 is provided on the side of the second liquid crystal layer 22 opposite to the first retardation layer 10 side.

[0027] The puncture modulus E2 of the second retardation layer 20 is 15 g / mm or less, may be 12 g / mm or less, may be 10 g / mm or less, or may be 9 g / mm or less. The puncture modulus E2 is usually 3 g / mm or more, may be 5 g / mm or more, or may be 7 g / mm or more. The puncture modulus E2 is a value at a temperature of 23°C and a relative humidity of 50%, and can be measured by a method for measuring the puncture modulus described in the examples described later. When the second retardation layer 20 is a laminate of the second liquid crystal layer 22 and the second alignment layer 21, the puncture modulus E2 of the second retardation layer 20 is measured by piercing the second alignment layer 21 side with a needle. In the second retardation layer 20, similar to the first retardation layer 10, the temperature dependency of the puncture modulus E2 is not observed in the range of 23 to 80°C.

[0028] The puncture modulus E2 of the second retardation layer 20 can be adjusted by, for example, the type and degree of polymerization (degree of curing) of the polymerizable liquid crystal compound constituting the second liquid crystal layer 22, the type and amount of additives such as a polymerization initiator, a reactive additive, a leveling agent, a polymerization inhibitor, and a crosslinking agent contained in the second liquid crystal layer 22, the type and degree of polymerization (degree of curing) of the polymerizable compound in the curable resin composition constituting the second alignment layer 21, the thickness of the second retardation layer 20, and the like. Usually, the value of the puncture modulus E2 increases as the degree of polymerization (degree of curing) increases. In addition, the puncture modulus E2 of the second retardation layer 20 can also be adjusted by the crosslink density of the second liquid crystal layer 22 and the crosslink density of the second alignment layer 21. For example, in order to increase the crosslink density of the second liquid crystal layer 22, a polyfunctional polymerizable liquid crystal compound having three or more polymerizable groups in the molecule may be used as the polymerizable liquid crystal compound for forming the second liquid crystal layer 22.

[0029] As a method of the preliminary experiment to set the puncture elastic modulus E2 of the second retardation layer 20 within a predetermined range, a method similar to the method of the preliminary experiment to set the puncture elastic modulus E1 of the first retardation layer described above within a desired range can be mentioned.

[0030] The thickness of the second retardation layer 20 is preferably 1.0 μm or more, may be 1.5 μm or more, may be 2.0 μm or more, or may be 2.5 μm or more. The thickness is usually 8 μm or less, may be 5 μm or less, may be 3.5 μm or less, or may be 3.0 μm or less.

[0031] It is considered that the smaller the puncture modulus E2 of the second phase difference layer 20, the softer the second phase difference layer 20. As described later, the optical laminates 1a and 1b can be obtained by separating the second base layer 25 from the optical laminates 1c and 1d. When the puncture modulus E2 of the second phase difference layer 20 is small, the second phase difference layer 20 is likely to follow the movement of peeling off the second base layer 25, and therefore the second base layer 25 is likely to be easily separated regardless of the separation speed of the second base layer 25. On the other hand, when the puncture modulus E2 is large, the second phase difference layer 20 is hardened, and it is considered that the second phase difference layer 20 is difficult to follow the movement of peeling off the second base layer 25. Therefore, depending on the separation speed of the second base layer 25, there is a risk of problems such as cracks occurring in the second phase difference layer 20 or breakage of the second base layer 25 when the second base layer 25 is separated.

[0032] In the optical laminate 1, since the puncture elastic modulus E2 of the second phase difference layer 20 is within the above-mentioned range, the second base layer 25 can be easily separated without depending on the separation speed of the second base layer 25. In particular, it is possible to suppress a large variation in the peel force required to separate the second base layer 25 depending on the separation speed of the second base layer 25. In contrast, if the puncture elastic modulus E2 of the second phase difference layer 20 is not within the above-mentioned range, the peel force varies greatly depending on the separation speed of the second base layer 25, and depending on the separation speed, the above-mentioned problems may occur.

[0033] The puncture elastic modulus E2 of the second phase difference layer 20 may be the same as or different from the puncture elastic modulus E1 of the first phase difference layer 10. By setting the puncture elastic modulus E2 of the second phase difference layer 20 in the above range, the second base material layer 25 can be easily separated favorably regardless of the separation speed. Therefore, the puncture elastic modulus E1 of the first phase difference layer 10 may be larger than the puncture elastic modulus E2 of the second phase difference layer 20.

[0034] In particular, in the optical laminates 1b and 1d, the puncture elastic modulus E1 of the first retardation layer 10 is preferably 15 g / mm or less. It is considered that the smaller the puncture elastic modulus E1 of the first retardation layer 10, the softer the first retardation layer 10. As described later, the manufacturing process of the optical laminate 1b includes a process of separating the first base layer 15 from a third laminate 63 (FIG. 6) having an optical film 40, a pressure-sensitive adhesive layer 31, the first retardation layer 10, and the first base layer 15 in this order. When the puncture elastic modulus E1 of the first retardation layer 10 is small, the first retardation layer 10 is more likely to follow the movement of peeling off the first base layer 15, and therefore the first base layer 15 is more likely to be separated well regardless of the separation speed of the first base layer 15. On the other hand, it is considered that when the puncture elastic modulus E1 increases, the first retardation layer 10 becomes hard and the first retardation layer 10 is less likely to follow the movement of peeling off the first base layer 15. Therefore, depending on the separation speed of the first base layer 15, there is a risk of problems such as cracks occurring in the first retardation layer 10 or breakage of the first base layer 15 when the first base layer 15 is separated.

[0035] In the optical laminates 1b and 1d, by setting the puncture elastic modulus E1 of the first retardation layer 10 to 15 g / mm or less, it is believed that the peel force is prevented from fluctuating greatly depending on the separation speed of the first base layer 15, and the first base layer 15 can be easily separated from the third laminate 63 (Figure 6) described later regardless of the separation speed.

[0036] The pressure-sensitive adhesive layer 31 is a layer for bonding the optical film 40 and the first retardation layer 10, and is a layer formed using a pressure-sensitive adhesive composition. It can be in direct contact with the retardation layer 10 .

[0037] The storage modulus of the adhesive layer 31 at a temperature of 23° C. is 3.0×10 6 N / m 2 It is preferable that the value is less than 2.5×10 6 N / m 2 It may be less than or equal to 2.0 x 10 6 N / m 2 It may be less than or equal to 1.0 x 10 6 N / m2 It may be less than 5 x 10 5 N / m 2 The storage modulus of the pressure-sensitive adhesive layer 31 at a temperature of 23° C. may be typically 1×10 5 N / m 2 That is 2 x 10 5 N / m 2 The storage modulus at a temperature of 23° C. can be measured by the method described in the examples below.

[0038] It is considered that the pressure-sensitive adhesive layer 31 easily follows the movement of peeling off the second base layer 25 when the storage modulus at a temperature of 23°C is within the above range. This makes it easy to separate the second base layer 25 well from the optical laminates 1c, 1d, regardless of the separation speed of the second base layer 25. On the other hand, when the storage modulus at a temperature of 23°C of the pressure-sensitive adhesive layer 31 is not within the above range, the pressure-sensitive adhesive layer 31 does not easily follow the movement of peeling off the second base layer 25, and depending on the separation speed of the second base layer 25, there is a risk of problems such as cracks occurring in the second retardation layer 20 or breakage of the second base layer 25 when the second base layer 25 is separated.

[0039] The storage modulus of the adhesive layer 31 at a temperature of 80° C. is 6.0×10 5 N / m 2 It is preferable that the value is less than 5.0×10 5 N / m 2 It may be less than or equal to 3.0 x 10 5 N / m 2 It may be less than or equal to 1.0 x 10 5 N / m 2 It may be less than 8 x 10 4 N / m 2 The storage modulus of the pressure-sensitive adhesive layer 31 at a temperature of 80° C. is usually 1×10 4 N / m 2 That's 3 x 10. 4 N / m 2 It may be more than 5 x 10 4 N / m 2The storage modulus at a temperature of 80° C. can be measured by the method described in the examples below.

[0040] When the storage modulus of the adhesive layer 31 at a temperature of 80°C is within the above range, the second base layer 25 can be easily separated from the optical laminates 1c, 1d regardless of the separation speed of the second base layer 25, for reasons similar to those explained regarding the storage modulus of the adhesive layer 31 at a temperature of 23°C.

[0041] The storage modulus of the adhesive layer 31 at temperatures of 23°C and 80°C can be adjusted by the type of adhesive contained in the adhesive composition, and when the adhesive is an active energy ray-curable adhesive, it can be adjusted by the degree of curing by irradiation with energy rays, etc.

[0042] Examples of the optical film 40 include a linear polarizing layer; a polarizing plate having a protective layer on one or both sides of the linear polarizing layer; a polarizing plate with a protective film on one side of the polarizing plate; a reflective film; a semi-transmissive reflective film; a brightness enhancing film; an optical compensation film; and a film with an anti-glare function, and one or more of these may be used in combination. The optical film 40 preferably includes at least a linear polarizing layer, and more preferably includes a polarizing plate. When the optical film 40 includes a polarizing plate having a protective layer only on one side of the linear polarizing layer, it is preferable that the linear polarizing layer side of the polarizing plate and the first retardation layer 10 are bonded together. When the optical film includes a polarizing plate with a protective film, it is preferable that the polarizing plate side of the polarizing plate with the protective film and the first retardation layer 10 are bonded together.

[0043] The attachment layer 32 is a layer for attaching the first retardation layer 10 and the second retardation layer 20. The attachment layer 32 can be in direct contact with the first retardation layer 10 and the second retardation layer 20. The attachment layer 32 can be a pressure-sensitive adhesive layer or an adhesive cured layer, and is preferably an adhesive cured layer.

[0044] The optical laminate 1 may be a circular polarizing plate. In this case, the optical film 40 is a linear polarizing plate. It is preferable that at least one of the first retardation layer 10 and the second retardation layer 20 is a quarter-wave retardation layer. When the optical laminate 1 is a circular polarizing plate, the layer structure of the optical laminate 1 may be, when the optical film 40 is a polarizing plate, [i] a polarizing plate, a half-wave retardation layer, and a quarter-wave retardation layer in this order, [ii] a polarizing plate, a quarter-wave retardation layer with reverse wavelength dispersion, and a positive C plate in this order, or [iii] a polarizing plate, a positive C plate, and a quarter-wave retardation layer with reverse wavelength dispersion in this order.

[0045] The optical laminate 1 can be used by being attached to an image display element of, for example, a liquid crystal display device or an organic EL (electroluminescence) display device.

[0046] (Method for producing the optical laminate of the first embodiment) 5 and 6 are schematic cross-sectional views showing an example of a manufacturing process of the optical laminate of this embodiment (first embodiment). The optical laminates 1a and 1b manufactured by the manufacturing method of the optical laminate 1 include the optical film 40, the pressure-sensitive adhesive layer 31, the first retardation layer 10, the attachment layer 32, and the second retardation layer 20 described above in this order. The second retardation layer 20 has the puncture elastic modulus E2 (puncture elastic modulus E(X)) described above. The pressure-sensitive adhesive layer 31 preferably has the storage elastic modulus at temperatures of 23°C and 80°C described above.

[0047] The method for producing the optical laminates 1a and 1b includes the steps of: A step of preparing a base layer-attached first retardation layer 18 having a first base layer 15 and a first retardation layer 10 (FIG. 5(a)); A step of preparing a base layer-attached second retardation layer 28 (base layer-attached retardation layer (X)) having a second base layer 25 (base layer (X)) and a second retardation layer 20 (retardation layer (X)) (FIG. 5(b)); A step of preparing a laminate having an optical film 40, a pressure-sensitive adhesive layer 31, a first retardation layer 10, an attachment layer 32, a second retardation layer 20, and a second base layer 25 in this order; and separating the second base layer 25 from the laminate. The first retardation layer 10, the attachment layer 32, and the second retardation layer 20 constitute a retardation layer-containing layer.

[0048] The method for producing the optical laminate 1 may further include a step of forming another adhesive layer other than the adhesive layer 31 and a release film in order from the exposed surface side exposed by the step of separating the second base layer 25. The other adhesive layer can be used, for example, for bonding to an image display element of a display device. The release film can cover and protect the surface of the other adhesive layer opposite to the second retardation layer 20 side, and can be provided releasably with respect to the other adhesive layer.

[0049] In the manufacturing method of the optical laminate 1, the second phase difference layer 20 has the puncture elastic modulus E2 in the above-mentioned range. Therefore, even when the second base layer 25 is separated, the occurrence of defects such as cracks in the second phase difference layer 20 or breakage of the second base layer 25 is suppressed, and the second base layer 25 can be easily separated satisfactorily.

[0050] The manufacturing method of the optical laminate 1 includes the above-mentioned steps, but the steps included in the step of preparing the laminate are different between the case of obtaining the optical laminate 1a shown in Fig. 1 and the case of obtaining the optical laminate 1b shown in Fig. 2. When obtaining the optical laminate 1a shown in Fig. 1, the puncture elastic modulus E1 of the first retardation layer 10 is not particularly limited, and for example, the first retardation layer 10 can have the puncture elastic modulus E1 described above. When obtaining the optical laminate 1b shown in Fig. 2, the puncture elastic modulus E1 of the first retardation layer 10 is preferably 15 g / mm or less as described above.

[0051] First, a process for preparing the laminate in order to obtain the optical laminate 1a shown in FIG. 1 will be described. In the method for producing the optical laminate 1a, the step of preparing the laminate includes the steps of: A step of preparing a base layer-attached first retardation layer 18 having a first base layer 15 and a first retardation layer 10 (FIG. 5(a)); A step of preparing a base layer-attached second retardation layer 28 having the above-mentioned second base layer 25 and the second retardation layer 20 (FIG. 5(b)); a step of bonding the first phase difference layer 10 side of the base layer-included first phase difference layer 18 and the second phase difference layer 20 side of the base layer-included second phase difference layer 28 via a bonding layer 32 (FIG. 5(c)); A step of separating the first base layer 15 after the step of bonding via the bonding layer 32 (FIG. 5(d)), The method may further include a step of bonding the optical film 40 to an exposed surface exposed by separating the first base layer 15 via a pressure-sensitive adhesive layer 31 (FIG. 5(e)).

[0052] The first retardation layer 10 includes a first liquid crystal layer 12 formed by polymerizing a polymerizable liquid crystal compound on a first base layer 15, and the second retardation layer 20 includes a second liquid crystal layer 22 (liquid crystal layer X) formed by polymerizing a polymerizable liquid crystal compound on a second base layer 25. Therefore, the step of preparing the base layer-attached first retardation layer 18 may include a step of polymerizing a polymerizable liquid crystal compound on the first base layer 15 to form the first liquid crystal layer 12. In addition, the step of preparing the base layer-attached second retardation layer 28 may include a step of polymerizing a polymerizable liquid crystal compound on the second base layer 25 to form the second liquid crystal layer 22.

[0053] The first liquid crystal layer 12 may be formed by polymerizing a polymerizable liquid crystal compound on the first alignment layer 11 provided on the first base layer 15. Similarly, the second liquid crystal layer 22 may be formed by polymerizing a polymerizable liquid crystal compound on the second alignment layer 21 provided on the second base layer 25. In this case, the step of preparing the base layer-attached first retardation layer 18 may include a step of forming the first alignment layer 11 on the first base layer 15. In addition, the step of preparing the base layer-attached second retardation layer 28 may include a step of forming the second alignment layer 21 on the second base layer 25.

[0054] In the manufacturing method of the optical laminate 1a (FIG. 1), the step of laminating via the lamination layer 32 includes, for example, first forming a lamination composition layer for forming the lamination layer 32 on the first phase difference layer 10 side of the base layer-attached first phase difference layer 18 and / or the second phase difference layer 20 side of the base layer-attached second phase difference layer 28. Next, the lamination layer 32 is formed from the lamination composition layer. The method for forming the lamination layer 32 from the lamination composition layer may be selected according to the type of the lamination composition layer. For example, when the lamination composition is an adhesive composition, the lamination layer 32 may be formed as an adhesive cured layer by curing the lamination by irradiating active energy rays or performing a heat treatment, etc., and when the lamination composition is a pressure-sensitive adhesive composition, the lamination composition layer may be used as the lamination layer 32, or the lamination layer 32 may be formed from the lamination composition layer. This allows for the production of a first laminate 61 in which the first base layer 15, the first retardation layer 10, the first bonding layer 30, the second retardation layer 20, and the second base layer 25 are laminated in this order, as shown in (c) of Figure 5.

[0055] In the first laminate 61, the first base layer 15 is preferably provided separably between the first base layer 15 and the first liquid crystal layer 12. Being separable between the first base layer 15 and the first liquid crystal layer 12 means that the first base layer 15 is peelable from the first liquid crystal layer 12, or, if the first alignment layer 11 is present between the first base layer 15 and the first liquid crystal layer 12, that the first alignment layer 11 is peelable from the first liquid crystal layer 11, or that the first alignment layer 11 is peelable from the first liquid crystal layer 12. Therefore, when the first base layer 15 is peelable from the first alignment layer 11, the first alignment layer 11 remains on the first liquid crystal layer 12 when the first base layer 15 is separated from the first laminate 61 as described later. When the first alignment layer 11 is peelable from the first liquid crystal layer 12, the first alignment layer 11 is peeled off together with the first base layer 15 when the first base layer 15 is separated from the first laminate 61.

[0056] In the step of separating the first base layer 15, the first base layer 15 is separated from the first laminate 61 obtained in the step of bonding via the bonding layer 32. In the step of separating the first base layer 15, only the first base layer 15 may be peeled off, or, if the first alignment layer 11 is present, the first alignment layer 11 may also be peeled off together with the first base layer 15. This results in a second laminate 62 in which the first retardation layer 10 (first alignment layer 11, first liquid crystal layer 12), the bonding layer 32, the second retardation layer 20 (second liquid crystal layer 22, second alignment layer 21), and the second base layer 25 are laminated in this order ((d) of FIG. 5).

[0057] In the step of laminating via the adhesive layer 31, for example, first, an adhesive composition layer is formed on the exposed surface side exposed by separating the first base layer 15 of the second laminate 62 shown in (d) of FIG. 5 and / or on the optical film 40. Next, the second laminate 62 and the optical film 40 are laminated via the adhesive composition layer, and the adhesive composition layer is made into the adhesive layer 31, or the adhesive layer 31 is formed from the adhesive composition layer. As a result, an optical laminate 1c in which the optical film 40, the adhesive layer 31, the first retardation layer 10 (first alignment layer 11, first liquid crystal layer 12), the lamination layer 32, the second retardation layer 20 (second liquid crystal layer 22, second alignment layer 21), and the second base layer 25 are laminated in this order is obtained ((e) of FIG. 5, FIG. 3).

[0058] In the manufacturing method of the optical laminate 1a shown in Fig. 1, in the step of separating the second base layer 25, the second base layer 25 is separated from the optical laminate 1c. In the step of separating the second base layer 25, only the second base layer 25 may be peeled off, or, if the second alignment layer 21 is present, the second alignment layer 21 may also be peeled off together with the second base layer 25. In this way, the optical laminate 1a shown in Fig. 1 can be obtained.

[0059] Next, a process for preparing the laminate in the case of obtaining the optical laminate 1b shown in Fig. 2 will be described. In the method for producing the optical laminate 1b, the process for preparing the laminate includes the following steps: A step of preparing a base layer-attached first retardation layer 18 having a first base layer 15 and a first retardation layer 10 (FIG. 5(a)); A step of preparing a base layer-attached second retardation layer 28 having the above-mentioned second base layer 25 and the second retardation layer 20 (FIG. 5(b)); a step of bonding the optical film 40 and the first retardation layer 10 side of the base layer-attached first retardation layer 18 via a pressure-sensitive adhesive layer 31 (FIG. 6(a)); A step of separating the first base layer 15 after the step of bonding via the pressure-sensitive adhesive layer 31 (FIG. 6(b)), It may include a step of bonding an exposed surface exposed by separating the first base layer 15 to the second retardation layer 20 side of the base layer-attached second retardation layer 28 via an attachment layer 32 (FIG. 6(c)).

[0060] The method for obtaining the first retardation layer 18 with the base layer and the second retardation layer 28 with the base layer can be the above-mentioned method. Fig. 6 shows a case where the first retardation layer 18 is a laminate of the first alignment layer 11 and the first liquid crystal layer 12, but the first retardation layer 18 does not need to include the first alignment layer 11. Similarly, Fig. 6 shows a case where the second retardation layer 28 is a laminate of the second alignment layer 21 and the second liquid crystal layer 22, but the second retardation layer 28 does not need to include the second alignment layer 21.

[0061] In the step of bonding via the pressure-sensitive adhesive layer 31, for example, first, a pressure-sensitive adhesive composition layer is formed on the first retardation layer 10 side of the substrate layer-attached first retardation layer 18 and / or on the optical film 40. Next, the substrate layer-attached first retardation layer 18 and the optical film 40 are laminated via the pressure-sensitive adhesive composition layer, and the pressure-sensitive adhesive layer 31 is formed from the pressure-sensitive adhesive composition layer. This provides a third laminate 63 in which the optical film 40, the pressure-sensitive adhesive layer 31, the first retardation layer 10 (first alignment layer 11, first liquid crystal layer 12), and the first substrate layer 15 are laminated in this order. (Figure 6(a)).

[0062] In the step of separating the first base layer 15, the first base layer 15 is separated from the laminate shown in (a) of FIG. 6. In the step of separating the first base layer 15, only the first base layer 15 may be separated, or if the first alignment layer 11 is present, the first alignment layer 11 may be peeled off together with the first base layer 15. When the puncture modulus E1 of the first retardation layer 10 is 15 g / mm or less, it is considered that even when the first base layer 15 is separated, defects such as cracks in the first retardation layer 10 or breakage of the first base layer 15 are suppressed, and the first base layer 15 can be easily separated. As a result, a fourth laminate 64 in which the optical film 40, the adhesive layer 31, and the first retardation layer 10 (the first liquid crystal layer 12, the first alignment layer 11) are laminated in this order is obtained ((b) of FIG. 6).

[0063] In the step of laminating via the lamination layer 32, for example, first, a lamination composition layer for forming the lamination layer 32 is formed on the exposed surface side exposed by separating the first base layer 15 of the fourth laminate 64 shown in (b) of FIG. 6, and / or on the second phase difference layer 20 side of the second phase difference layer 28 with the base layer. Next, the fourth laminate 64 and the second phase difference layer 28 with the base layer are laminated via the lamination composition layer, and then the lamination layer 32 is formed from the lamination composition layer. The method of forming the lamination layer 32 from the lamination composition layer includes the above-mentioned methods. As a result, an optical laminate 1d in which the optical film 40, the pressure-sensitive adhesive layer 31, the first phase difference layer 10 (the first liquid crystal layer 12, the first alignment layer 11), the lamination layer 32, the second phase difference layer 20 (the second liquid crystal layer 22, the second alignment layer 21), and the second base layer 25 are laminated in this order is obtained ((c) of FIG. 6, FIG. 4).

[0064] In the manufacturing method of the optical laminate 1b shown in Fig. 2, in the step of separating the second base layer 25, the second base layer 25 is separated from the optical laminate 1d. In the step of separating the second base layer 25, only the second base layer 25 may be peeled off, or, if the second alignment layer 21 is present, the second alignment layer 21 may also be peeled off together with the second base layer 25. In this way, the optical laminate 1b shown in Fig. 2 can be obtained.

[0065] (Optical laminate of the second embodiment) 7 and 8 are schematic cross-sectional views showing an example of the optical laminate of this embodiment (second embodiment). The optical laminates 2a and 2b of this embodiment (hereinafter, these may be collectively referred to as "optical laminate 2") include an optical film 40, a pressure-sensitive adhesive layer 31, and a retardation layer (X) 50, in this order, as shown in Figs. 7 and 8. The retardation layer (X) 50 includes a liquid crystal layer (X) 52 which is a cured layer of a polymerizable liquid crystal compound. The retardation layer (X) 50 has a puncture elastic modulus E(X) of 15 g / mm or less.

[0066] 8, the optical laminate 2 may have a base layer (X) 55 on the side of the retardation layer (X) opposite to the pressure-sensitive adhesive layer 31. The base layer (X) 55 is preferably provided separably between the base layer (X) 55 and the liquid crystal layer (X) 52 included in the retardation layer (X) 50.

[0067] The term "separable" between the substrate layer (X) 55 and the liquid crystal layer (X) 52 means that the substrate layer (X) 55 is peelable from the liquid crystal layer (X) 52, or, when an alignment layer (X) 51 is present between the substrate layer (X) 55 and the liquid crystal layer (X) 52, the substrate layer (X) 55 is peelable from the alignment layer (X) 51, or the alignment layer (X) 51 is peelable from the liquid crystal layer (X) 52. Therefore, when the substrate layer (X) 55 is peelable from the alignment layer (X) 51, the alignment layer (X) 51 remains on the liquid crystal layer (X) 52 when the substrate layer (X) 55 is separated from the optical laminate 2b (FIG. 8) (FIG. 7). When the alignment layer (X) 51 is peelable from the liquid crystal layer (X) 52, the alignment layer (X) 51 is peeled off together with the substrate layer (X) 55 when the substrate layer (X) 55 is separated from the optical laminate 2b.

[0068] The retardation layer (X) may be a liquid crystal layer (X) 52 itself, which is a cured layer of a polymerizable liquid crystal compound, or may be a laminate of the liquid crystal layer (X) 52 and an alignment layer (X) 51. When the retardation layer (X) 50 has an alignment layer (X) 51, the alignment layer (X) 51 is provided on the side of the liquid crystal layer (X) 52 opposite to the pressure-sensitive adhesive layer 31 side.

[0069] The puncture modulus E(X) of the retardation layer (X) 50 is 15 g / mm or less, may be 12 g / mm or less, may be 10 g / mm or less, or may be 9 g / mm or less. The puncture modulus E(X) is usually 3 g / mm or more, may be 5 g / mm or more, or may be 7 g / mm or more. The puncture modulus E(X) is a value at a temperature of 23°C and a relative humidity of 50%, and can be measured according to the procedure of the puncture modulus measurement method described in the examples below. When the retardation layer (X) 50 is a laminate of the liquid crystal layer (X) 52 and the alignment layer (X) 51, the puncture modulus E(X) of the retardation layer (X) 50 is measured by piercing the layer from the alignment layer (X) 51 side with a needle. In the retardation layer (X) 50, the temperature dependency of the puncture modulus E(X) is not observed in the range of 23 to 80°C.

[0070] As a method for adjusting the puncture elastic modulus E(X) of the retardation layer (X) 50 and a method for a preliminary experiment for setting the puncture elastic modulus E(X) within a predetermined range, the methods described above for the puncture elastic moduli E1 and E2 of the first retardation layer 10 and the second retardation layer 20 can be mentioned.

[0071] The thickness of the retardation layer (X) 50 is preferably 1.0 μm or more, more preferably 1.5 μm or more, may be 1.7 μm or more, or may be 2.0 μm or more. The thickness of the retardation layer (X) 50 is usually 8 μm or less, may be 5 μm or less, may be 3.5 μm or less, or may be 3.0 μm or less.

[0072] It is considered that the smaller the puncture elastic modulus E(X) of the retardation layer (X) 50, the softer the retardation layer (X) 50. As described later, the optical laminate 2a can be obtained by separating the base layer (X) 55 from the optical laminate 2b. When the puncture elastic modulus E(X) of the retardation layer (X) 50 is small, the retardation layer (X) 50 is likely to follow the movement of peeling off the base layer (X) 55, and therefore the base layer (X) 55 is likely to be favorably separated regardless of the separation speed of the base layer (X) 55. On the other hand, when the puncture elastic modulus E(X) is large, the retardation layer (X) 50 is hardened, and it is considered that the retardation layer (X) 50 is difficult to follow the movement of peeling off the base layer (X) 55. Therefore, depending on the separation speed of the base layer (X) 55, problems such as cracks occurring in the retardation layer (X) 50 or breakage of the base layer (X) 55 may occur when the base layer (X) 55 is separated.

[0073] In the optical laminate 2, since the puncture elastic modulus E(X) of the retardation layer (X) 50 is within the above range, the base layer (X) 55 can be easily separated well regardless of the separation speed of the base layer (X) 55. In particular, it is possible to suppress a large variation in the peel force required to separate the base layer (X) 55 depending on the separation speed of the base layer (X) 55. In contrast, if the puncture elastic modulus E(X) of the retardation layer (X) 50 is not within the above range, the peel force varies greatly depending on the separation speed of the base layer (X) 55, and depending on the separation speed, the above-mentioned problems may occur.

[0074] The pressure-sensitive adhesive layer 31 is a layer for bonding the optical film 40 and the retardation layer (X) together, and is a layer formed using a pressure-sensitive adhesive composition. The pressure-sensitive adhesive layer 31 can be in direct contact with the optical film 40 and the retardation layer (X).

[0075] The pressure-sensitive adhesive layer 31 preferably has the above-described storage modulus at temperatures of 23° C. and 80° C. It is considered that when the storage modulus of the pressure-sensitive adhesive layer 31 at a temperature of 23° C. is in the above-described range, the pressure-sensitive adhesive layer 31 can easily follow the movement of peeling off the base layer (X) 55. This allows the base layer (X) 55 to be easily and satisfactorily separated from the optical laminate 2b, regardless of the separation speed of the base layer (X) 55. On the other hand, if the storage modulus of the adhesive layer 31 at a temperature of 23° C. is not within the above range, the adhesive layer 31 will be less likely to follow the movement of peeling off the base layer (X) 55, and depending on the separation speed of the base layer (X) 55, there is a risk of problems such as cracks occurring in the retardation layer (X) 50 or breakage of the base layer (X) 55 during separation of the base layer (X) 55. In addition, by having the storage modulus of the adhesive layer 31 at a temperature of 80° C. within the above range, the base layer (X) 55 can be easily and satisfactorily separated from the optical laminate 2b, regardless of the separation speed of the base layer (X) 55, for the same reasons as those explained regarding the storage modulus of the adhesive layer 31 at a temperature of 23° C.

[0076] As the optical film 40, the above-mentioned films can be used.

[0077] The optical laminate 2 may be a circular polarizing plate. In this case, the optical film 40 includes a linear polarizing layer, a polarizing plate, or a polarizing plate with a protective film, and the retardation layer (X) 50 is a 1 / 4 wavelength retardation layer or a 1 / 4 wavelength retardation layer with reverse wavelength dispersion. The optical laminate 2 can be used by being attached to an image display element of a liquid crystal display device or an organic EL (electroluminescence) display device, for example.

[0078] (Method for producing optical laminate according to the second embodiment) The optical laminate 2a manufactured by the manufacturing method of the optical laminate 2 includes the above-described optical film 40, pressure-sensitive adhesive layer 31, and retardation layer (X) 50 in this order. The retardation layer (X) 50 has the above-described puncture elastic modulus E(X). The pressure-sensitive adhesive layer 31 preferably has the above-described storage elastic modulus at temperatures of 23°C and 80°C.

[0079] The method for producing the optical laminate 2a includes the steps of: A step of preparing a substrate-layer-attached retardation layer (X) having a substrate layer (X) 55 and a retardation layer (X) 50; The retardation layer (X) 50 includes a liquid crystal layer (X) 52 formed by polymerizing a polymerizable liquid crystal compound on a base layer (X) 55, A step of preparing a laminate having an optical film 40, a pressure-sensitive adhesive layer 31, a retardation layer (X), and a base layer (X) 55 in this order (FIG. 8); and separating the base layer (X) 55 from the laminate.

[0080] In the method for producing the optical laminate 2, the retardation layer (X) 50 has a puncture elastic modulus E(X) within the above-mentioned range. Therefore, even when the base layer (X) 55 is separated, problems such as cracks in the retardation layer (X) 50 and breakage of the base layer (X) 55 are suppressed, and the base layer (X) 55 can be easily and satisfactorily separated.

[0081] The retardation layer (X) includes a liquid crystal layer (X) 52 formed by polymerizing a polymerizable liquid crystal compound on a base layer (X) 55. Therefore, the step of preparing the base layer-attached retardation layer (X) may include a step of polymerizing a polymerizable liquid crystal compound on the base layer (X) 55 to form the liquid crystal layer (X) 52. The liquid crystal layer (X) 52 may be formed by polymerizing a polymerizable liquid crystal compound on an alignment layer (X) 51 provided on the base layer (X) 55. In this case, the step of preparing the base layer-attached retardation layer (X) may include a step of forming the alignment layer (X) 51 on the base layer (X) 55.

[0082] The step of preparing the laminate can include a step of bonding the optical film 40 and the retardation layer (X) 50 side of the substrate layer-attached retardation layer (X) via a pressure-sensitive adhesive layer 31. The step of bonding via the pressure-sensitive adhesive layer 31 includes, for example, first forming a pressure-sensitive adhesive composition layer on the retardation layer (X) 50 side of the substrate layer-attached retardation layer (X) and / or the optical film 40. Next, the substrate layer-attached retardation layer (X) and the optical film 40 are laminated via the pressure-sensitive adhesive composition layer, and the pressure-sensitive adhesive composition is applied to the optical film 40. Alternatively, the pressure-sensitive adhesive layer 31 is formed from a pressure-sensitive adhesive composition layer. This provides an optical laminate 2b in which the optical film 40, the pressure-sensitive adhesive layer 31, and the retardation layer (X) 50 (the alignment layer (X) 51, the liquid crystal layer (X) 52) are laminated in this order (FIG. 8).

[0083] In the step of separating the base layer (X) 55, the base layer (X) 55 is separated from the optical laminate 2b. In the step of separating the base layer (X) 55, only the base layer (X) 55 may be peeled off, or, if the alignment layer (X) 52 is present, the alignment layer (X) 52 may also be peeled off together with the base layer (X) 55. In this way, the optical laminate 2a shown in FIG. 7 can be obtained.

[0084] The method for producing the optical laminate 2a may further include a step of forming another adhesive layer other than the adhesive layer 31 and a release film in order from the exposed surface side exposed by the step of separating the base layer (X) 55. The other adhesive layer can be used, for example, for bonding to an image display element of a display device. The release film can cover and protect the surface of the other adhesive layer opposite to the retardation layer (X) 50 side, and can be provided releasably with respect to the other adhesive layer.

[0085] Hereinafter, the optical laminate of this embodiment and each member used in the method for producing the same will be described in detail.

[0086] (1st retardation layer, 2nd retardation layer, retardation layer (X)) The first retardation layer, the second retardation layer, and the retardation layer (X) (hereinafter, these may be collectively referred to as "retardation layers") are layers having retardation properties, and include a first liquid crystal layer, a second liquid crystal layer, and a liquid crystal layer (X), which are cured layers of a polymerizable liquid crystal compound, respectively. The first retardation layer may have a first alignment layer in addition to the first liquid crystal layer. Similarly, the second retardation layer may have a second alignment layer in addition to the second liquid crystal layer. Similarly, the retardation layer (X) may have an alignment layer (X) in addition to the liquid crystal layer (X).

[0087] (First liquid crystal layer, second liquid crystal layer, and liquid crystal layer (X)) The first liquid crystal layer, the second liquid crystal layer, and the liquid crystal layer (X) (hereinafter, these may be collectively referred to as "liquid crystal layers") are cured layers of a polymerizable liquid crystal compound. As the polymerizable liquid crystal compound, a rod-shaped polymerizable liquid crystal compound and a disk-shaped polymerizable liquid crystal compound can be used, and one of these may be used, or a mixture containing both of these may be used. When the rod-shaped polymerizable liquid crystal compound is aligned horizontally or vertically to the base layer (the first base layer, the second base layer, or the base layer (X)), the optical axis of the polymerizable liquid crystal compound coincides with the long axis direction of the polymerizable liquid crystal compound. When the disk-shaped polymerizable liquid crystal compound is aligned, the optical axis of the polymerizable liquid crystal compound exists in a direction perpendicular to the disk surface of the polymerizable liquid crystal compound. As the rod-shaped polymerizable liquid crystal compound, for example, those described in JP-A-11-513019 (claim 1, etc.) can be suitably used. As the disc-shaped polymerizable liquid crystal compound, those described in JP-A-2007-108732 (paragraphs

[0020] to

[0067] , etc.) and JP-A-2010-244038 (paragraphs

[0013] to

[0108] , etc.) can be suitably used.

[0088] In order for the liquid crystal layer formed by polymerizing the polymerizable liquid crystal compound to exhibit an in-plane retardation, the polymerizable liquid crystal compound may be aligned in a suitable direction. When the polymerizable liquid crystal compound is rod-shaped, the in-plane retardation is exhibited by aligning the optical axis of the polymerizable liquid crystal compound horizontally to the substrate layer plane, in which case the optical axis direction and the slow axis direction coincide. When the polymerizable liquid crystal compound is disc-shaped, the in-plane retardation is exhibited by aligning the optical axis of the polymerizable liquid crystal compound horizontally to the substrate layer plane, in which case the optical axis and the slow axis are perpendicular to each other. The alignment state of the polymerizable liquid crystal compound can be adjusted by the combination of the alignment layer and the polymerizable liquid crystal compound.

[0089] The polymerizable liquid crystal compound is a compound having at least one polymerizable group and having liquid crystal properties. In the case where two or more kinds of polymerizable liquid crystal compounds are used in combination, it is preferable that at least one of them has two or more polymerizable groups in the molecule. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group means a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator described later. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, an oxetanyl group, a styryl group, and an allyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferable, and an acryloyloxy group is more preferable. The liquid crystal property of the polymerizable liquid crystal compound may be a thermotropic liquid crystal or a lyotropic liquid crystal, and when the thermotropic liquid crystal is classified according to the degree of order, it may be a nematic liquid crystal or a smectic liquid crystal.

[0090] The thickness of the liquid crystal layer is not particularly limited, but is preferably 0.5 μm or more, may be 1 μm or more, and is usually 8 μm or less, may be 5 μm or less, and is preferably 3 μm or less.

[0091] (First alignment layer, second alignment layer, alignment layer (X)) The first alignment layer, the second alignment layer, and the alignment layer (X) (hereinafter, these may be collectively referred to as "alignment layers") have an alignment regulating force that aligns the polymerizable liquid crystal compound contained in the liquid crystal layer formed on these alignment layers in a desired direction. It is preferable that the alignment layers have solvent resistance that does not dissolve the liquid crystal layer-forming composition described below by coating, etc., and have heat resistance to removal of the solvent and heat treatment for orienting the polymerizable liquid crystal compound.

[0092] The alignment layer may be a vertical alignment layer in which the molecular axis of the polymerizable liquid crystal compound is aligned vertically relative to the base layer, a horizontal alignment layer in which the molecular axis of the polymerizable liquid crystal compound is aligned horizontally relative to the base layer, or an inclined alignment layer in which the molecular axis of the polymerizable liquid crystal compound is aligned at an inclination relative to the base layer.

[0093] Examples of the alignment layer include an alignment polymer layer formed of an alignment polymer, a photoalignment polymer layer formed of a photoalignment polymer, and a groove alignment layer having a concave-convex pattern or a plurality of grooves on the layer surface. The first alignment layer, the second alignment layer, and the alignment layer (X) may be the same alignment layer or different alignment layers.

[0094] The oriented polymer layer can be formed by applying a composition in which an oriented polymer is dissolved in a solvent to a substrate layer (first substrate layer, second substrate layer, or substrate layer (X)), removing the solvent, and optionally performing a rubbing treatment. In this case, the orientation control force of the oriented polymer layer formed from the oriented polymer can be arbitrarily adjusted by the surface state of the oriented polymer and the rubbing conditions.

[0095] The photoalignable polymer layer can be formed by applying a composition containing a polymer or monomer having a photoreactive group and a solvent to a substrate layer (first substrate layer, second substrate layer, or substrate layer (X)) and irradiating it with light such as ultraviolet light. In particular, when an alignment control force is to be exerted in the horizontal direction, the layer can be formed by irradiating it with polarized light. In this case, the alignment control force in the photoalignable polymer layer can be arbitrarily adjusted by, for example, the conditions for irradiating the photoalignable polymer with polarized light.

[0096] The groove alignment layer can be formed, for example, by a method of forming a concave-convex pattern by exposing the surface of a photosensitive polyimide film through an exposure mask having slits in a pattern shape, developing, etc., a method of forming an uncured layer of active energy ray curable resin on a plate-shaped master having grooves on the surface, transferring this layer to a base layer (first base layer or second base layer) and curing it, a method of transferring an active energy ray curable resin to a base layer, etc. It can be formed by a method in which an uncured layer of resin is formed, and then a roll-shaped master having projections and recesses is pressed against this layer to form projections and recesses, followed by curing.

[0097] The alignment layer preferably contains a resin formed by polymerizing a polymerizable compound, from the viewpoint that the alignment layer can be easily peeled off and removed together with the substrate layer when the alignment layer is peeled off and removed together with the substrate layer. The above-mentioned polymerizable compound is a compound having a polymerizable group, and is usually a non-liquid crystal polymerizable non-liquid crystal compound that does not become liquid crystal. The polymerizable groups of the polymerizable compound react with each other to polymerize the polymerizable compound, thereby forming a resin.

[0098] When the alignment layer is to be peeled off and removed together with the substrate layer, the alignment layer preferably contains a resin which is a cured product obtained by curing a known monofunctional or polyfunctional (meth)acrylate monomer in the presence of a polymerization initiator. Examples of (meth)acrylate monomers include 2-ethylhexyl acrylate, cyclohexyl acrylate, diethylene glycol mono 2-ethylhexyl ether acrylate, diethylene glycol monophenyl ether acrylate, tetraethylene glycol monophenyl ether acrylate, trimethylolpropane triacrylate, lauryl acrylate, lauryl methacrylate, isobornyl acrylate, isobornyl methacrylate, 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxypropyl acrylate, benzyl acrylate, tetrahydrofurfuryl methacrylate, 2-hydroxyethyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, methacrylic acid, urethane acrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, dipentaerythritol polyacrylate, and dipentaerythritol hexaacrylate. The resin may be one of these, or a mixture of two or more. When such a resin is used as an alignment layer, before or after the step of laminating the obtained laminate with other layers such as a polarizing plate after forming a liquid crystal layer, when the substrate layer is separated from the retardation layer with substrate layer (the first retardation layer with substrate layer, the second retardation layer with substrate layer, or the retardation layer with substrate layer (X)), the alignment layer can be peeled off and removed together with the substrate layer. In this specification, "(meth)acrylic" means either acrylic or methacrylic. "(meth)" in (meth)acrylate, etc., has the same meaning.

[0099] In the case where the alignment layer is not peeled off together with the substrate layer and remains on the liquid crystal layer side, it is preferable that the alignment layer contains a resin such as a cured product obtained by curing a trifunctional or higher (meth)acrylate monomer, an imide monomer or a vinyl ether monomer, and it is more preferable that the alignment layer contains a cured product obtained by curing a trifunctional or higher (meth)acrylate monomer.

[0100] When the alignment layer is formed by curing the polymerizable compound in the composition for forming the alignment layer by irradiation with ultraviolet light, the light irradiation intensity of the ultraviolet light is not particularly limited, but is preferably 10 to 1,000 mW / cm 2 is preferably 100 to 600 mW / cm 2 It is more preferable that the light irradiation intensity of the composition for forming an alignment layer applied on the base layer is 10 mW / cm. 2 If it is less than 1,000mW / cm, the reaction time will be too long and 2 When the temperature exceeds 100°C, the heat radiated from the light source The occurrence of wrinkles in the base layer may cause uneven phase difference. The irradiation intensity is an intensity in a wavelength region effective for activating a polymerization initiator, preferably a photoradical polymerization initiator, more preferably an intensity in a wavelength region of 400 nm or less, and further preferably an intensity in a wavelength region of 280 to 320 nm. Irradiation is performed once or multiple times with such light irradiation intensity, and the accumulated light amount is 10 mJ / cm. 2 or more, preferably 100 to 1,000 mJ / cm 2 , more preferably 400 to 1,000 mJ / cm 2 , and more preferably 600 to 1,000 mJ / cm 2 , and especially preferably 600 to 1,000 mJ / cm 2 It is preferable to set the thickness of the composition for forming the alignment layer applied on the substrate layer. The calculated light intensity is 10mJ / cm 2 If the cumulative light amount is less than 1,000 mJ / cm 2 , the generation of active species derived from the polymerization initiator is insufficient, and the curing of the composition for forming an alignment layer is insufficient. 2If the irradiation time exceeds this range, the irradiation time becomes extremely long, which is disadvantageous in improving productivity. The wavelength of light irradiation (UVA (320 to 390 nm), UVB (280 to 320 nm), etc.) varies depending on the thickness and type of the base layer, the types of components contained in the composition for forming an alignment layer, and the combination of components in the composition for forming an alignment layer, and the like, and the cumulative amount of light required also changes depending on the wavelength of light irradiation.

[0101] When the polymerizable compound in the composition for forming an alignment layer is cured by ultraviolet irradiation, the temperature during ultraviolet irradiation is preferably 25° C. or higher, more preferably 50° C. or higher, and even more preferably 80° C. or higher, from the viewpoint of sufficiently increasing the degree of polymerization. In addition, if the temperature is too high, wrinkles may occur in the base layer, and there is a concern that unevenness in retardation may occur. Therefore, the temperature during ultraviolet irradiation is preferably 200° C. or lower, more preferably 150° C. or lower, and even more preferably 120° C. or lower. The above upper and lower limits can be combined in any combination.

[0102] The thickness of the alignment layer is not particularly limited, but is preferably 0.01 μm or more, may be 0.05 μm or more, or may be 0.1 μm or more, and is usually 5 μm or less, may be 2.5 μm or less, or may be 1 μm or less.

[0103] (First retardation layer with base layer, second retardation layer with base layer, retardation layer with base layer (X)) The first retardation layer with a substrate layer, the second retardation layer with a substrate layer, and the retardation layer with a substrate layer (X) (hereinafter, these may be collectively referred to as "retardation layers with a substrate layer") can be obtained by applying a liquid crystal layer-forming composition containing a polymerizable liquid crystal compound onto the substrate layer, drying the composition, and polymerizing the polymerizable liquid crystal compound to form a liquid crystal layer, which is a cured layer formed by polymerizing the polymerizable liquid crystal compound. When an alignment layer is formed on the substrate layer, the liquid crystal layer-forming composition may be applied onto the alignment layer, and when the liquid crystal layer has a multilayer structure of two or more layers, the liquid crystal layer-forming composition may be applied sequentially to form a multilayer structure. The above-mentioned method may be used to form the alignment layer.

[0104] The liquid crystal layer forming composition usually contains a solvent in addition to the polymerizable liquid crystal compound. The liquid crystal layer forming composition may further contain a polymerization initiator, a reactive additive, a polymerization inhibitor, etc. Each of these components may be used alone or in combination of two or more.

[0105] The solvent that may be contained in the composition containing the polymerizable liquid crystal compound is preferably a solvent that can dissolve the polymerizable liquid crystal compound and is inactive in the polymerization reaction of the polymerizable liquid crystal compound.

[0106] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, propylene glycol monomethyl ether, and phenol; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, cycloheptanone, methyl amyl ketone, methyl isobutyl ketone, and N-methyl-2-pyrrolidinone; non-chlorinated aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; non-chlorinated aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as propylene glycol monomethyl ether, tetrahydrofuran, and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. The solvents may be used alone or in combination.

[0107] The content of the solvent in the polymerizable liquid crystal composition is usually 10 to 100 parts by mass of the solid content. The content is preferably from 50 to 5000 parts by mass, and more preferably from 50 to 5000 parts by mass. The solid content means the total of the components other than the solvent in the polymerizable liquid crystal composition.

[0108] The polymerization initiator that may be contained in the composition containing the polymerizable liquid crystal compound is a compound that can initiate the polymerization reaction of the polymerizable liquid crystal compound, and a photopolymerization initiator is preferred because it can initiate the polymerization reaction under lower temperature conditions. Specifically, a photopolymerization initiator that can generate active radicals or acids by the action of light is included, and among them, a photopolymerization initiator that generates radicals by the action of light is preferred. Examples of the photoradical polymerization initiator include benzoin compounds, benzophenone compounds, benzyl ketal compounds, α-hydroxyketone compounds, α-aminoketone compounds, oxime compounds, triazine compounds, iodonium salts, and sulfonium salts. As the photoradical polymerization initiator, only one type may be used, or two or more types may be used in combination.

[0109] Commercially available products may be used as the photoradical polymerization initiator. Specific examples of such commercially available products include Irgacure (registered trademark) 907, Irgacure 184, Irgacure 651, Irgacure 819, Irgacure 250, Irgacure 369, Irgacure 379, Irgacure 127, Irgacure 2959, Irgacure 754, Irgacure 379EG (all manufactured by BASF Japan Ltd.), Seikuol BZ, Seikuol Z, Seikuol BEE (all manufactured by Seiko Chemical Co., Ltd.), Kayacure Examples of such compounds include (kayacure) BP100 (manufactured by Nippon Kayaku Co., Ltd.), Kayacure UVI-6992 (manufactured by Dow Chemical Co., Ltd.), ADEKA OPTOMER SP-152, ADEKA OPTOMER SP-170, ADEKA OPTOMER N-1717, ADEKA OPTOMER N-1919, ADEKA ARCLES NCI-831, ADEKA ARCLES NCI-930 (all manufactured by ADEKA Corporation), TAZ-A, TAZ-PP (all manufactured by Nippon SiberHegner AG), and TAZ-104 (manufactured by Sanwa Chemical Co., Ltd.).

[0110] The content of the polymerization initiator is usually 0.1 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 1 to 15 parts by mass, based on 100 parts by weight of the total amount of the polymerizable liquid crystal compound. Within this range, the reaction of the polymerizable group proceeds sufficiently, and the alignment state of the polymerizable liquid crystal compound is easily stabilized.

[0111] The crosslinking agent that may be contained in the composition containing the polymerizable liquid crystal compound is a compound having one or more photo- or heat-reactive groups in the molecule. By using the crosslinking agent, the crosslinking density of the liquid crystal layer changes, and the film strength can be easily adjusted. Examples of the crosslinking agent include polyfunctional acrylate compounds, epoxy compounds, oxetane compounds, methylol compounds, isocyanate compounds, and the like. Among them, polyfunctional acrylate compounds are preferred from the viewpoint of uniformity of the coating film and film strength adjustment. The crosslinking agent preferably has 2 to 8 reactive groups in the molecule, and more preferably has 2 to 6 polymerizable groups in the molecule.

[0112] Commercially available products may be used as the polyfunctional acrylate. Specific examples of such commercially available products include A-DOD-N, A-HD-N, A-NOD-N, APG-100, APG-200, APG-400, A-GLY-9E, A-GLY-20E, A-TMM-3, A-TMPT, AD-TMP, ATM-35E, A-TMMT, A-9550, A-DPH, HD-N, NOD-N, NPG, TMPT (manufactured by Shin-Nakamura Chemical Co., Ltd.), "ARONIX M-220”, “M-325”, “M-240”, “M-270”, “M-309”, “M-310”, “M-321”, same "M-350", "M-360", "M-305", "M-306", "M-450", "M-451", "M-408" ", "M-400", "M-402", "M-403", "M-404", "M-405", "M-406" (manufactured by Toagosei Co., Ltd.), "EBECRYL11", "145", "150", "40", "140", "180", DPGDA, H Examples include DDA, TPGDA, HPNDA, PETIA, PETRA, TMPTA, TMPEOTA, DPHA, and EBECRYL series (manufactured by Daicel-Cytec Co., Ltd.).

[0113] The content of the crosslinking agent is preferably 1 to 30 parts by mass, and more preferably 3 to 20 parts by mass, relative to 100 parts by mass of the total amount of the polymerizable liquid crystal compound. If the content of the crosslinking agent is below the lower limit, problems are likely to occur during processing such as polishing, and if it is above the upper limit, the alignment state of the liquid crystal compound becomes unstable, and alignment defects are likely to occur.

[0114] The reactive additive that may be contained in the composition containing the polymerizable liquid crystal compound is preferably one having a carbon-carbon unsaturated bond and an active hydrogen reactive group in its molecule. The "active hydrogen reactive group" here means a group that is reactive to a group having active hydrogen such as a carboxyl group (-COOH), a hydroxyl group (-OH), or an amino group (-NH2), and representative examples thereof include a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group. The number of carbon-carbon unsaturated bonds and active hydrogen reactive groups that the reactive additive has in its molecule is usually 1 to 20, and preferably 1 to 10.

[0115] In the reactive additive, it is preferable that at least two active hydrogen reactive groups are present in the molecule. In this case, the multiple active hydrogen reactive groups present may be the same or different.

[0116] The carbon-carbon unsaturated bond in the molecule of the reactive additive refers to a carbon-carbon double bond or a carbon-carbon triple bond, and is preferably a carbon-carbon double bond. Among them, the reactive additive preferably contains a carbon-carbon unsaturated bond in the molecule as a vinyl group and / or a (meth)acrylic group. Furthermore, the active hydrogen reactive group is preferably at least one selected from the group consisting of an epoxy group, a glycidyl group, and an isocyanate group. In particular, a reactive additive having an acrylic group as the carbon-carbon double bond and an isocyanate group as the active hydrogen reactive group is particularly preferred.

[0117] Examples of reactive additives include compounds having a (meth)acrylic group and an epoxy group, such as methacryloxyglycidyl ether and acryloxyglycidyl ether; compounds having a (meth)acrylic group and an oxetane group, such as oxetane acrylate and oxetane methacrylate; compounds having a (meth)acrylic group and a lactone group, such as lactone acrylate and lactone methacrylate; compounds having a vinyl group and an oxazoline group, such as vinyl oxazoline and isopropenyl oxazoline; compounds having a (meth)acrylic group and an isocyanate group, such as isocyanatomethyl acrylate, isocyanatomethyl methacrylate, 2-isocyanatoethyl acrylate and 2-isocyanatoethyl methacrylate, and oligomers of these monomers. In addition, compounds having a vinyl group or a vinylene group and an acid anhydride, such as methacrylic anhydride, acrylic anhydride, maleic anhydride, and vinyl maleic anhydride, can be mentioned. Among these, methacryloxyglycidyl ether, acryloxyglycidyl ether, isocyanatomethyl acrylate, isocyanatomethyl methacrylate, vinyloxazoline, 2-isocyanatoethyl acrylate, 2-isocyanatoethyl methacrylate, or oligomers of these monomers are preferred, and isocyanatomethyl acrylate, 2-isocyanatoethyl acrylate, or oligomers of these monomers are particularly preferred.

[0118] When the polymerizable liquid crystal composition contains a reactive additive, the content thereof is usually 0.1 parts by mass or more and 30 parts by mass or less, and preferably 0.1 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0119] The composition containing the polymerizable liquid crystal compound may contain a leveling agent in order to make the coating film obtained by applying the composition flatter. Examples of the leveling agent include silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents.

[0120] The content of the leveling agent is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily aligned, and the obtained liquid crystal cured film (cured layer of the polymerizable liquid crystal compound) tends to be smoother, which is preferable.

[0121] The liquid crystal layer forming composition can be applied by a known method such as a coating method such as a spin coating method, an extrusion method, a gravure coating method, a die coating method, a slit coating method, a bar coating method, an applicator method, or a printing method such as a flexography method. After applying the liquid crystal layer forming composition, it is preferable to remove the solvent under conditions in which the polymerizable liquid crystal compound contained in the coating layer does not polymerize. Examples of the drying method include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0122] The polymerization of the polymerizable liquid crystal compound carried out after drying of the coating layer can be carried out by a known method of polymerizing a compound having a polymerizable functional group. Examples of the polymerization method include thermal polymerization and photopolymerization, and photopolymerization is preferable from the viewpoint of ease of polymerization. When polymerizing the polymerizable liquid crystal compound by photopolymerization, it is preferable to use a liquid crystal layer forming composition containing a photopolymerization initiator, coat and dry this liquid crystal layer forming composition, align the polymerizable liquid crystal compound contained in the dried coating after drying, and perform photopolymerization while maintaining this liquid crystal alignment state.

[0123] Photopolymerization can be carried out by irradiating the polymerizable liquid crystal compound in the dried film with active energy rays. The active energy rays to be irradiated can be appropriately selected depending on the type and amount of polymerizable groups in the polymerizable liquid crystal compound, the type of photopolymerization initiator, etc., and can include, for example, one or more active energy rays selected from the group consisting of visible light, ultraviolet light, laser light, X-rays, α-rays, β-rays, and γ-rays. Among these, ultraviolet light is preferred because it is easy to control the progress of the polymerization reaction and photopolymerization devices that are widely used in this field can be used, and it is preferable to select the type of polymerizable liquid crystal compound and photopolymerization initiator so that photopolymerization can be performed by ultraviolet light. In photopolymerization, the polymerization temperature can also be controlled by irradiating the active energy rays while cooling the dried film with an appropriate cooling means.

[0124] When the coating layer of the liquid crystal layer-forming composition is cured by ultraviolet irradiation, the irradiation intensity of the ultraviolet light is not particularly limited, but is preferably 10 to 1,000 mW / cm. 2 is preferably 100 to 600 mW / cm 2 It is more preferable that the light irradiation intensity on the coating layer is 10 mW / cm 2 If it is less than 1,000mW / cm, the reaction time will be too long and 2 When it exceeds Heat radiated from the substrate may cause wrinkles in the substrate layer, resulting in uneven phase difference. The irradiation intensity is an intensity in a wavelength region effective for activating a polymerization initiator, preferably a photoradical polymerization initiator, more preferably an intensity in a wavelength region of 400 nm or less, and further preferably an intensity in a wavelength region of 280 to 320 nm. Irradiation is performed once or multiple times with such light irradiation intensity, and the accumulated light amount is 10 mJ / cm2. 2 or more, preferably 100 to 1,000 mJ / cm 2 , more preferably 400 to 1,000 mJ / cm 2 , more preferably 600 to 1000 mJ / cm 2 , and especially preferably 600 to 1,000 mJ / cm 2It is preferable to set the integrated light amount to the coating layer to 10 mJ / cm 2 If the cumulative light amount is less than 1,000 mJ / cm2, the generation of active species derived from the polymerization initiator is insufficient, and the curing of the coating layer is insufficient. 2 If the exposure time exceeds The wavelength of light irradiation (UVA (320 to 390 nm), UVB (280 to 320 nm), etc.) varies depending on the thickness and type of the base layer, the types of components contained in the composition for forming a liquid crystal layer, and the combination of components in the composition for forming a liquid crystal layer, and the integrated amount of light required also changes depending on the wavelength of light irradiation.

[0125] When the coating layer of the liquid crystal layer forming composition is cured by ultraviolet irradiation, from the viewpoint of sufficiently increasing the degree of polymerization, the temperature during ultraviolet irradiation is preferably 25° C. or higher, more preferably 50° C. or higher, and even more preferably 80° C. or higher. If the temperature is too high, wrinkles may occur in the base layer, and there is a concern that unevenness in retardation may occur. Therefore, the temperature during ultraviolet irradiation is preferably 200° C. or lower, more preferably 150° C. or lower, and even more preferably 120° C. or lower. The above upper and lower limits can be combined in any combination.

[0126] (1st base material layer, 2nd base material layer, base material layer (X)) The first substrate layer, the second substrate layer, and the substrate layer (X) (hereinafter, these may be collectively referred to as "substrate layers") function as support layers that support the alignment layer and the liquid crystal layer, which will be described later, formed on these substrate layers. The substrate layer is preferably a film formed of a resin material.

[0127] As the resin material, for example, a resin material excellent in transparency, mechanical strength, thermal stability, stretchability, etc. is used. Specifically, polyolefin-based resins such as polyethylene and polypropylene; cyclic polyolefin-based resins such as norbornene-based polymers; polyester-based resins such as polyethylene terephthalate (PET) and polyethylene naphthalate; (meth)acrylic acid-based resins such as polymethyl (meth)acrylate; cellulose ester-based resins such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; vinyl alcohol-based resins such as polyvinyl alcohol and polyvinyl acetate; polycarbonate-based resins; polystyrene-based resins; polyarylate-based resins; polysulfone-based resins; polyethersulfone-based resins; polyamide-based resins; polyimide-based resins; polyether ketone-based resins; polyphenylene sulfide-based resins; polyphenylene oxide-based resins, and mixtures and copolymers thereof can be mentioned. Among these resins, it is preferable to use any one of cyclic polyolefin-based resins, polyester-based resins, cellulose ester-based resins, and (meth)acrylic acid-based resins, or mixtures thereof.

[0128] The thickness of the base layer is not particularly limited, but in general, from the viewpoint of strength and workability such as handleability, it is preferably 1 to 300 μm, more preferably 10 to 200 μm, and even more preferably 30 to 120 μm.

[0129] When the first retardation layer with a substrate layer has a first alignment layer, or when the second retardation layer with a substrate layer has a second alignment layer, in order to improve the adhesion between the first substrate layer and the first alignment layer and between the second substrate layer and the second alignment layer, at least the surface of the first substrate layer on which the first alignment layer is formed and at least the surface of the second substrate layer on which the second alignment layer is formed may be subjected to corona treatment, plasma treatment, flame treatment, or the like, or a primer layer or the like may be formed.

[0130] The substrate layer is peelable from the liquid crystal layer or the alignment layer, and the magnitude of the peel force between the substrate layer and the liquid crystal layer or the alignment layer needs to be determined taking into consideration the order in which the substrate layers are separated. The peel force of the first substrate layer, which is separated first from the first laminate, is preferably smaller than the peel force of the second substrate layer, which is separated later.

[0131] (Adhesive layer, other adhesive layer) The adhesive layer and the other adhesive layer (hereinafter, both may be collectively referred to simply as "adhesive layers") refer to layers composed of an adhesive composition. These adhesives exhibit adhesive properties by being attached to an adherend such as a polarizing plate or a liquid crystal layer, and are known as pressure-sensitive adhesives. The degree of crosslinking and adhesive strength of the active energy ray-curable pressure-sensitive adhesives described below can be adjusted by irradiating them with energy rays.

[0132] As the adhesive, any adhesive having excellent optical transparency that is known in the art can be used without any particular limitation, and for example, an adhesive having a base polymer such as an acrylic, urethane, silicone, or polyvinyl ether can be used. In addition, an active energy ray curable adhesive, a heat curable adhesive, or the like may be used. Among these, an adhesive having an acrylic resin as a base polymer, which is excellent in transparency, adhesive strength, removability (hereinafter also referred to as reworkability), weather resistance, heat resistance, and the like, is preferable. The adhesive layer is preferably composed of a reaction product of an adhesive composition containing a (meth)acrylic resin, a crosslinking agent, and a silane compound, and may contain other components.

[0133] The adhesive layer may be formed using an active energy ray curable adhesive. The active energy ray curable adhesive is prepared by blending an ultraviolet ray curable compound such as a multifunctional acrylate into an adhesive composition, forming an adhesive layer, and then curing the adhesive layer by irradiating it with ultraviolet rays, thereby forming a harder adhesive layer. The active energy ray curable adhesive has a property of being cured by irradiation with energy rays such as ultraviolet rays and electron beams. The active energy ray curable adhesive has adhesiveness even before irradiation with energy rays, so it is an adhesive that has a property of being able to adhere to an adherend such as an optical film or a retardation layer, and to be cured by irradiation with energy rays to adjust the adhesion.

[0134] An active energy ray-curable pressure-sensitive adhesive generally contains an acrylic pressure-sensitive adhesive and an energy ray-polymerizable compound as main components, and usually further contains a crosslinking agent, and may also contain a photopolymerization initiator, a photosensitizer, etc., as necessary.

[0135] The thickness of the adhesive layer is preferably 3 μm or more, more preferably 5 μm or more. The thickness of the adhesive layer is preferably 40 μm or less, more preferably 30 μm or less. The above upper and lower limits can be combined in any combination.

[0136] (Lamination layer) The attachment layer may be a pressure-sensitive adhesive layer or a cured adhesive layer. The pressure-sensitive adhesive layer may be any of those described above. The cured adhesive layer may be formed using an adhesive composition.

[0137] The adhesive cured layer refers to an adhesive cured layer formed by curing a curable component in an adhesive composition. The adhesive composition for forming the adhesive cured layer is an adhesive other than a pressure-sensitive adhesive (adhesive), and examples thereof include water-based adhesives and active energy ray curable adhesives. Examples of water-based adhesives include adhesives in which a polyvinyl alcohol resin is dissolved or dispersed in water. Examples of active energy ray curable adhesives include solvent-free active energy ray curable adhesives containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. By using a solvent-free active energy ray curable adhesive, the adhesion between layers can be improved. On the other hand, if the active energy ray curable adhesive contains a solvent (especially an organic solvent), sufficient adhesion cannot be obtained even if the curable component contained in the adhesive is the same, and when the optical laminate is cut to a predetermined size, problems such as peeling at the end of the adhesive tend to occur. In addition, since a process of drying the solvent is added, additional shrinkage stress due to heat is applied, and curling may easily occur in the optical laminate.

[0138] As an active energy ray curable adhesive, it shows good adhesive properties and is a cationic polymer. It is preferable that the active energy ray-curable adhesive contains either one or both of a cationic polymerization initiator and a radical polymerization initiator for initiating a curing reaction of the curable compound.

[0139] Examples of the cationic polymerizable curable compound include an epoxy compound (a compound having one or more epoxy groups in the molecule), an oxetane compound (a compound having one or more oxetane rings in the molecule), or a combination thereof.

[0140] Examples of the radically polymerizable curable compound include (meth)acrylic compounds (compounds having one or more (meth)acryloyloxy groups in the molecule), other vinyl compounds having a radically polymerizable double bond, or combinations thereof.

[0141] The active energy ray curable adhesive may contain a sensitizer as necessary. By using a sensitizer, the reactivity is improved, and the mechanical strength and adhesive strength of the adhesive cured layer can be further improved. As the sensitizer, a known sensitizer can be appropriately applied. When a sensitizer is added, the amount of the sensitizer is preferably in the range of 0.1 to 20 parts by mass with respect to 100 parts by mass of the total amount of the active energy ray curable adhesive.

[0142] The active energy ray-curable adhesive may contain additives such as an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow adjuster, a plasticizer, an antifoaming agent, an antistatic agent, a leveling agent, and a solvent, as necessary.

[0143] The adhesive composition layer may be formed by applying the adhesive composition to the bonding surface of the first retardation layer with the base layer or the second retardation layer with the base layer. As the application method, a normal coating technique using a die coater, a comma coater, a reverse roll coater, a gravure coater, a rod coater, a wire bar coater, a doctor blade coater, an air doctor coater, or the like may be adopted.

[0144] When a water-based adhesive is used, the drying method is not particularly limited, but for example, a drying method using a hot air dryer or an infrared dryer can be used.

[0145] When an active energy ray curable adhesive is used, the adhesive composition layer can be cured by irradiating it with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays to form an adhesive cured layer. As the active energy ray, ultraviolet rays are preferred, and as the light source in this case, low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, chemical lamps, black light lamps, microwave excited mercury lamps, metal halide lamps, etc. can be used.

[0146] The thickness of the cured adhesive layer is, for example, 0.01 μm or more, optionally 0.05 μm or more, or optionally 0.5 μm or more, and is usually 5 μm or less, optionally 3 μm or less, or optionally 2 μm or less.

[0147] (Linear polarizing layer) The linearly polarizing layer has a property of transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis when unpolarized light is incident on the linearly polarizing layer. The linearly polarizing layer may contain a polyvinyl alcohol (hereinafter sometimes abbreviated as "PVA")-based resin film, or may be a cured film obtained by aligning a dichroic dye in a polymerizable liquid crystal compound and polymerizing the polymerizable liquid crystal compound.

[0148] Examples of the linear polarizing layer containing a PVA-based resin film include a PVA-based film, a partially formalized PVA-based film, and an ethylene-vinyl acetate copolymer partially saponified film. Examples of the linear polarizing layer include a hydrophilic polymer film that has been dyed with a dichroic substance such as iodine or a dichroic dye, and then stretched. In view of its excellent optical properties, it is preferable to use a linear polarizing layer obtained by dyeing a PVA-based resin film with iodine and uniaxially stretching the film.

[0149] PVA resins can be produced by saponifying polyvinyl acetate resins. Polyvinyl acetate resins can be copolymers of vinyl acetate and other monomers copolymerizable with vinyl acetate, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and acrylamides having an ammonium group.

[0150] The saponification degree of the PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can also be used. The polymerization degree of the polyvinyl alcohol resin is usually about 1,000 to 10,000, preferably about 1,500 to 5,000.

[0151] Such a PVA-based resin is used as a raw film for the linear polarizing layer. The method for forming the PVA-based resin film is not particularly limited, and the film can be formed by a known method. The thickness of the PVA-based resin raw film is, for example, about 10 to 100 μm, preferably about 10 to 60 μm, and more preferably about 15 to 30 μm.

[0152] Other methods for producing a linearly polarizing layer containing a PVA-based resin film include a method including the steps of first preparing a substrate film, applying a solution of a resin such as a PVA-based resin onto the substrate film, and then drying the substrate film to remove the solvent to form a resin layer on the substrate film. A primer layer can be formed in advance on the surface of the substrate film on which the resin layer is to be formed. A resin film such as PET can be used as the substrate film. Examples of materials for the primer layer include PVA resin crosslinked with a hydrophilic resin used in the linearly polarizing layer.

[0153] Next, the amount of solvent such as water in the resin layer is adjusted as necessary, and then the base film and the PVA resin layer are uniaxially stretched, and then the PVA resin layer is dyed with a dichroic dye such as iodine to adsorb and align the dichroic dye in the PVA resin layer. Next, if necessary, the PVA resin layer with the dichroic dye adsorbed and oriented is treated with an aqueous boric acid solution, and a washing step is performed to wash off the aqueous boric acid solution. This produces a PVA resin layer with the dichroic dye adsorbed and oriented, that is, a film of a linear polarizing layer. A known method can be used for each step.

[0154] The uniaxial stretching of the substrate film and the PVA resin layer may be performed before dyeing, during dyeing, or during boric acid treatment after dyeing, and uniaxial stretching may be performed at each of these multiple stages. The substrate film and the PVA resin layer may be uniaxially stretched in the MD direction (film transport direction), in which case they may be uniaxially stretched between rolls with different peripheral speeds, or may be uniaxially stretched using a heated roll. The substrate film and the PVA resin layer may be uniaxially stretched in the TD direction (direction perpendicular to the film transport direction), in which case a so-called tenter method can be used. The substrate film and the PVA resin layer may be stretched by dry stretching in the air, or by wet stretching in a state in which the PVA resin layer is swollen with a solvent. In order to exhibit the performance of the linearly polarizing layer, the stretching ratio is 4 times or more, preferably 5 times or more, and particularly preferably 5.5 times or more. There is no particular upper limit to the stretching ratio, but it is preferably 8 times or less from the viewpoint of suppressing breakage and the like.

[0155] The linearly polarizing layer produced by the above method is laminated with a protective layer, which will be described later, and then the substrate film is peeled off. According to this method, the linear polarizing layer can be made even thinner.

[0156] As a method for producing a linearly polarizing layer which is a cured film obtained by orienting a dichroic dye in a polymerizable liquid crystal compound and polymerizing the polymerizable liquid crystal compound, there can be mentioned a method in which a composition for forming a polarizing layer containing a polymerizable liquid crystal compound and a dichroic dye is applied onto a substrate film, and the polymerizable liquid crystal compound is polymerized and cured while maintaining the liquid crystal state to form a linearly polarizing layer. The linearly polarizing layer thus obtained is in a state of being laminated on the substrate film, and the linearly polarizing layer with the substrate film may be used as a polarizing plate described later.

[0157] As the dichroic dye, a dye having different absorbance in the long axis direction and absorbance in the short axis direction of the molecule can be used, and for example, a dye having a maximum absorption wavelength (λmax) in the range of 300 to 700 nm is preferable. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, anthraquinone dyes, etc., and among them, azo dyes are preferable. Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, stilbene azo dyes, etc., and bisazo dyes and trisazo dyes are more preferable.

[0158] The composition for forming a polarizing layer may contain a solvent, a polymerization initiator such as a photopolymerization initiator, a photosensitizer, a polymerization inhibitor, and the like. The polymerizable liquid crystal compound, dichroic dye, solvent, polymerization initiator, photosensitizer, polymerization inhibitor, and the like contained in the composition for forming a polarizing layer may be a known one, and may be, for example, one exemplified in JP-A-2017-102479 and JP-A-2017-83843. In addition, the polymerizable liquid crystal compound may be the same as the compound exemplified as the polymerizable liquid crystal compound used to obtain the liquid crystal layer (first liquid crystal layer, second liquid crystal layer) described later. The method for forming a linear polarizing layer using the composition for forming a polarizing layer may also be the method exemplified in the above publication.

[0159] The thickness of the linearly polarizing layer is preferably 2 μm or more, more preferably 3 μm or more. The thickness of the linearly polarizing layer is 25 μm or less, preferably 15 μm or less, more preferably 13 μm or less, and further preferably 7 μm or less. The above upper and lower limits can be combined in any combination.

[0160] (Polarizing plate) A polarizing plate can be formed by laminating a protective layer on one or both sides of the linearly polarizing layer via a known adhesive layer or adhesive cured layer. This polarizing plate is a so-called linear polarizing plate. As the protective layer that can be laminated on one or both sides of the linearly polarizing layer, for example, a film formed from a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, stretchability, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose; polyester resins such as PET and polyethylene naphthalate; polyethersulfone resins; polysulfone resins; polycarbonate resins; polyamide resins such as nylon and aromatic polyamide; polyimide resins; polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin resins having cyclo- and norbornene structures (also called norbornene-based resins); (meth)acrylic resins; polyarylate resins; polystyrene resins; polyvinyl alcohol resins, and mixtures thereof. When protective layers are laminated on both sides of the linearly polarizing layer, the resin compositions of the two protective layers may be the same or different.

[0161] A film formed from a thermoplastic resin may be subjected to a surface treatment (e.g., corona treatment, etc.) to improve adhesion with the linear polarizing layer made of a PVA-based resin and a dichroic material, and a thin layer such as a primer layer (also called an undercoat layer) may be formed.

[0162] The protective layer may be, for example, the above-mentioned thermoplastic resin that has been stretched, or may not be stretched (hereinafter, may be referred to as "unstretched resin"). Examples of the stretching treatment include uniaxial stretching and biaxial stretching.

[0163] The thickness of the protective layer is preferably 3 μm or more, and more preferably 5 μm or more. The thickness of the protective layer is preferably 50 μm or less, and more preferably 30 μm or less. The above upper and lower limit values ​​can be combined in any combination.

[0164] The surface of the protective layer opposite to the linear polarizing layer may have a surface treatment layer, such as a hard coat layer, an antireflection layer, an anti-sticking layer, an anti-glare layer, a diffusion layer, etc. The surface treatment layer may be a separate layer laminated on the protective layer, or may be formed by applying a surface treatment to the surface of the protective layer.

[0165] The thickness of the polarizing plate is not particularly limited, but is usually 2 μm or more and 300 μm or less. The thickness of the polarizing plate may be 10 μm or more, and may be 150 μm or less, 120 μm or less, or 80 μm or less.

[0166] (Polarizing plate with protective film) A polarizing plate can be made into a polarizing plate with a protective film by laminating a protective film on one side of the polarizing plate. The protective film may be a resin film for a protective film on which an adhesive layer is formed, or may be formed of a self-adhesive film. The thickness of the protective film may be, for example, 30 to 200 μm, preferably 40 to 150 μm, and more preferably 50 to 120 μm.

[0167] Examples of the resin constituting the resin film for protective film include polyolefin resins such as polyethylene resins and polypropylene resins; cyclic polyolefin resins; polyester resins such as PET and polyethylene naphthalate; polycarbonate resins; (meth)acrylic resins, etc. Among these, polyester resins such as PET are preferred. The resin film for protective film may have a single layer structure, or may have a multilayer structure of two or more layers.

[0168] A self-adhesive film is a film that can adhere by itself and maintain its adhesion state without the need for a means for adhesion of an adhesive layer, etc. The self-adhesive film can be formed using, for example, a polypropylene-based resin, a polyethylene-based resin, or the like.

[0169] The thickness of the polarizing plate with the protective film is preferably 32 μm or more and 500 μm or less. The thickness of the polarizing plate with the protective film may be 40 μm or more, and may be 350 μm or less, 200 μm or less, or 150 μm or less.

[0170] (Release film) The release film covers and protects other adhesive layers or supports other adhesive layers, and functions as a separator that can be peeled off from other adhesive layers. Examples of the release film include a film in which a release treatment such as silicone treatment has been applied to the surface of the adhesive layer side of the substrate film. Examples of the resin material constituting the substrate film include the same resin material as the above-mentioned resin material constituting the protective layer. The resin film may have a single layer structure, or may be a multilayer resin film having a multilayer structure of two or more layers. EXAMPLES

[0171] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "%" and "parts" are by mass % and parts by mass unless otherwise specified.

[0172] [Measurement of puncture elasticity] (Preparation of measurement samples) The retardation layer with the substrate layer (the first retardation layer with the substrate layer, the second retardation layer with the substrate layer, or the retardation layer with the substrate layer (X)) used in the examples and comparative examples was cut into a size of 40 mm x 40 mm, which was used as a cut-out piece. A glued mount of 40 mm x 40 mm was also prepared. The glued mount was cut out in a square of 30 mm x 30 mm in the center. The cut-out piece was attached to the glued mount so that the surface of the retardation layer (the first retardation layer, the second retardation layer, or the retardation layer (X)) of the cut-out piece was in contact with the glue on the glued mount. Next, the substrate layer (the first substrate layer, the second substrate layer, or the substrate layer (X)) was separated from the cut-out piece to prepare a measurement sample for the puncture elastic modulus E2.

[0173] (Determination of puncture modulus) A needle with a tip diameter of 1 mmφ and 0.5R was attached to a handy compression tester ("NDG5 piercing tester needle penetration force measurement specification", manufactured by Kato Tech Co., Ltd.). The needle was pierced vertically into the retardation layer surface of the measurement sample from the retardation layer side of the measurement sample (the side opposite to the adhesive mount side) at a piercing speed of 0.33 cm / sec. The strain amount S [mm] at the stress F [g] just before the measurement sample broke due to this piercing was calculated, and the value of stress F [g] / strain amount S [mm] was calculated. This operation was performed for each of the five measurement samples, and the average value was determined as the piercing elastic modulus [g / mm]. The measurement was performed in an environment of a temperature of 23°C and a relative humidity of 50%.

[0174] [Measurement of storage modulus of adhesive layer] The storage modulus of the adhesive layer was measured at temperatures of 23°C and 80°C using a cylindrical piece with a diameter of 8 mm and a thickness of 1 mm as a test specimen, using a viscoelasticity measuring device "DYNAMIC ANARYZER RDA II" manufactured by REOMETRIC, by the torsional shear method at a frequency of 1 Hz.

[0175] [Evaluation of peelability] (Peel test of second base layer) The first base layer was separated from the first laminate prepared in Examples 1 and 2 and Comparative Examples 1 and 2, and the exposed surface was formed with the adhesive layer used in the preparation of the optical laminate of the above Examples and Comparative Examples. This was cut into a size of 25 mm wide x about 150 mm long, and the adhesive layer surface was then attached to a glass plate to prepare a test sample (1). One end of a peeling tape with a width of 25 mm x length of about 180 mm was attached to one side of the width of 25 mm on the surface of the second base layer of the test sample (1), and the other end was fixed to the gripping part of a tensile tester, and a peeling test was performed to peel off the second base layer, and the peeling force was measured. The peeling test was performed at a separation speed (crosshead speed (gripping movement speed)) of 300 mm / min, 15000 mm / min, and 30000 mm / min, and in each case, the peeling angle was 180°, and the test was performed under an environment of a temperature of 23°C and a relative humidity of 50%. For the peel test at a separation speed of 300 m / min, an "AGS-50NX" (manufactured by Shimadzu Corporation) was used as the tensile tester, and for the peel tests at separation speeds of 15,000 mm / min and 30,000 mm / min, a "TJ95-001" (manufactured by Imada Manufacturing Co., Ltd.) was used as the tensile tester.

[0176] (Peel test of base layer (X)) The adhesive layer used in the preparation of the optical laminate of the above-mentioned Examples and Comparative Examples was formed on the retardation layer (X) side of the retardation layer (X) with the substrate layer used in Example 3 and Comparative Examples 3 and 4, and cut into a size of 25 mm wide x about 150 mm long, and then the adhesive layer surface was attached to a glass plate to obtain a test sample (2). One end of a peeling tape with a width of 25 mm x length of about 180 mm was attached to one side of the substrate layer (X) surface of the test sample (2) with a width of 25 mm, and the other end was fixed to the gripping part of a tensile tester, and a peeling test was performed to peel off the substrate layer (X), and the peeling force was measured. The peeling test was performed at a separation speed (crosshead speed (gripping movement speed)) of 300 mm / min, 15000 mm / min, and 30000 mm / min, and in each case, the peeling angle was 180°, and the temperature was 23°C and the relative humidity was 50%. For the peel test at a separation speed of 300 m / min, an "AGS-50NX" (manufactured by Shimadzu Corporation) was used as the tensile tester, and for the peel tests at separation speeds of 15,000 mm / min and 30,000 mm / min, a "TJ95-001" (manufactured by Imada Manufacturing Co., Ltd.) was used as the tensile tester.

[0177] (Evaluation of separation speed dependency) In the peel tests of the second base layer and base layer (X), the peel force at a separation speed of 300 mm / min was defined as P(0.3), the peel force at 15,000 mm / min as P(15), and the peel force at 30,000 mm / min as P(30), and the ratios P(0.3) / P(15) and P(30) / P(15) were calculated. The closer the ratio is to 1, the smaller the dependency of the peel force on the separation speed when peeling the second base layer or base layer (X) is.

[0178] [Evaluation of retardation layer] After the peel test, the surface on the second retardation layer side or the base layer (X) side was visually observed to check for the presence or absence of cracks.

[0179] [Comparative Example 1 (Comparative Example of Optical Laminate Having First Retardation Layer and Second Retardation Layer)] [Preparation of the first retardation layer with the base layer] (Preparation of Photo-Alignment Layer-Forming Composition (1)) The following components were mixed, and the resulting mixture was stirred at a temperature of 80° C. for 1 hour to obtain a composition for forming a photoalignment layer (1). Photoalignment material (compound represented by the following formula): 5 parts [ka] Solvent (cyclopentanone): 95 parts

[0180] (Preparation of Liquid Crystal Layer Forming Composition (A-1)) A liquid crystal layer forming composition (A-1) was obtained by mixing the following components and stirring the resulting mixture at 80° C. for 1 hour. Polymerizable liquid crystal compound A1 and polymerizable liquid crystal compound A2 were synthesized by the method described in JP-A-2010-31223. Polymerizable liquid crystal compound A1 (compound represented by the following formula): 80 parts [ka] Polymerizable liquid crystal compound A2 (compound represented by the following formula): 20 parts [ka] Polymerization initiator (2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure 369; manufactured by Ciba Specialty Chemicals)): 6 parts Solvent (cyclopentanone): 400 parts

[0181] (Preparation of the first retardation layer with the base layer) A polyethylene terephthalate (PET) film (first base layer) having a thickness of 100 μm was treated once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) under conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The corona-treated surface was coated with a photoalignment layer-forming composition (1) using a bar coater, dried at 80° C. for 1 minute, and then irradiated with 100 mJ / cm 2 using a polarized UV irradiation device (SPOT CURE SP-7, manufactured by Ushio Inc.). 2A photo-alignment layer (first alignment layer) was obtained by exposing the film to polarized UV light with an integrated light amount of 100 nm. The thickness of the photo-alignment layer was measured with a laser microscope (LEXT, manufactured by Olympus Corporation) and found to be 100 nm.

[0182] Next, the liquid crystal layer-forming composition (A-1) was applied onto the photoalignment layer using a bar coater and dried at 120°C for 1 minute. After that, the composition was irradiated with ultraviolet light using a high-pressure mercury lamp (Unicur VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, wavelength: 365 nm, irradiation intensity at a wavelength of 365 nm: 10 mW / cm 2 , Accumulated light intensity: 2000mJ / cm 2 ) to form a first liquid crystal layer, thereby obtaining a first retardation layer with a substrate layer. The thickness of the obtained first liquid crystal layer was measured with a laser microscope (LEXT, manufactured by Olympus Corporation) and found to be 2.0 μm. When the PET film (first substrate layer) was separated from the first retardation layer with a substrate layer, the peeling interface was between the photoalignment layer and the first liquid crystal layer, the thickness of the first retardation layer (first liquid crystal layer) was 2.0 μm, and the puncture elastic modulus E1 of the first retardation layer was 39.9 g / mm.

[0183] [Preparation of second retardation layer (1) with base layer] (Preparation of composition for forming alignment layer (2)) 2-butoxyethanol was added to Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.), which is a commercially available alignment polymer, to obtain an alignment layer forming composition (2). The solid content of composition (2) was 1% relative to the total amount of the composition, and the solvent content relative to the total amount of the composition was 99%. The solid content of SunEver SE-610 was calculated from the concentration stated in the delivery specifications.

[0184] (Preparation of Liquid Crystal Layer Forming Composition (B-1)) The following components were mixed, and the resulting mixture was stirred at 80° C. for 1 hour and then cooled to room temperature to obtain a liquid crystal layer forming composition (B-1). Polymerizable liquid crystal compound (LC242, manufactured by BASF): 19.2% [ka] Polymerization initiator (Irgacure® 907, manufactured by BASF Japan): 0.5%; Reaction additive (Laromer® LR-9000, manufactured by BASF Japan): 1.1% Solvent (propylene glycol 1-monomethyl ether 2-acetate): 79.1%

[0185] (Preparation of second retardation layer (1) with base layer) A 38 μm thick polyethylene terephthalate (PET) film (second substrate layer) was treated once using a corona treatment device (AGF-B10, manufactured by Kasuga Electric Co., Ltd.) under the conditions of an output of 0.3 kW and a treatment speed of 3 m / min. The surface that had been subjected to the corona treatment was coated with the composition for forming an alignment layer (2) using a bar coater and dried at 90° C. for 1 minute to obtain an alignment layer (second alignment layer). The thickness of the obtained alignment layer was measured with a laser microscope (LEXT, manufactured by Olympus Corporation) and found to be 2.2 μm.

[0186] Next, the liquid crystal layer-forming composition (B-1) was applied onto the alignment layer using a bar coater and dried at 90°C for 1 minute, after which ultraviolet light was irradiated using a high-pressure mercury lamp (Unicur VB-15201BY-A, manufactured by Ushio Inc.) (under a nitrogen atmosphere, wavelength: 365 nm, accumulated light amount at wavelength 365 nm: 1000 mJ / cm 2 ) to form a second liquid crystal layer, thereby obtaining a second retardation layer (1) with a substrate layer. The thickness of the second liquid crystal layer in the second retardation layer (1) with a substrate layer was 0.8 μm. When the PET film (second substrate layer) was separated from the second retardation layer (1) with a substrate layer, the peeling interface was between the PET film and the alignment layer, the thickness of the second retardation layer (alignment layer and second liquid crystal layer) was 3.0 μm, and the puncture elastic modulus E2 of the second retardation layer was 36.0 g / mm.

[0187] [Preparation of optical film] As the optical film, a polarizing plate having a linear polarizing layer and protective layers on both sides thereof was prepared.

[0188] [Preparation of adhesive composition] The cationic curable components a1 to a3 shown in [a] to [c] below, and the cationic polymerization initiator and sensitizer shown in [d] and [e] below were mixed and then degassed to prepare a photocurable adhesive composition. The parts shown below are the amounts of each material in the adhesive composition. [a] Cationic curing component a1 3',4'-Epoxycyclohexylmethyl 3',4'-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 70 parts (solid content) [b] Cationic curing component a2 Neopentyl glycol diglycidyl ether (product name: EX-211, Nagase Chemte Manufactured by OX Co., Ltd.): 20 parts (solid content) [c] Cationic curing component a3 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts (solid content) [d] Cationic polymerization initiator 50% propylene carbonate solution of "CPI-100" (manufactured by San-Apro Co., Ltd.): 2.25 parts (solid content) [e] Sensitizer 1,4-diethoxynaphthalene: 2 parts (solid content)

[0189] (Preparation of the first laminate) The surface of the first retardation layer with the substrate layer on the first retardation layer side and the surface of the second retardation layer with the substrate layer on the second retardation layer side were subjected to corona treatment (treatment conditions: 800 W, 10 m / min, bar width 700 mm, 1 pass). The adhesive composition prepared above was applied to the corona-treated surface of the first retardation layer with the substrate layer using a coater (bar coater, manufactured by Daiichi Rika Co., Ltd.) to form an adhesive composition layer. This adhesive composition layer and the corona-treated surface of the second retardation layer with the substrate layer (1) were bonded using a bonding device (LPA3301, manufactured by Fujipla Co., Ltd.). Thereafter, a belt conveyor-equipped ultraviolet irradiation device (the lamp used was "H bulb" manufactured by Fusion UV Systems Co., Ltd.) was used to apply ultraviolet light from the second substrate layer side of the second retardation layer with the substrate layer (1) at an irradiation intensity of 390 mW / cm in the UVA region. 2 , the cumulative light intensity is 420mJ / cm 2 So, in the UVB range, it is 400mW / cm 2 , the cumulative light intensity is 400mJ / cm 2 The adhesive composition layer was cured by irradiation with ultraviolet light so as to obtain a first laminate.

[0190] The first laminate was used to evaluate the separation speed dependency of the peel force according to the procedure for measuring the peel force of the second base layer. The results are shown in Table 1.

[0191] (Preparation of optical laminate) The first base layer was separated from the first laminate, and the surface exposed by separating the first base layer was bonded to the optical film via a pressure-sensitive adhesive layer ("NCF #L2" manufactured by Lintec Corporation, a sheet-like pressure-sensitive adhesive having a thickness of 5 μm) having the storage modulus shown in Table 1 to obtain an optical laminate. The peeled interface when the first base layer was separated from the first laminate was between the first alignment layer and the first liquid crystal layer.

[0192] [Example 1 (Optical Laminate 1)] [Preparation of second retardation layer (2) with base layer] (Preparation of Liquid Crystal Layer Forming Composition (B-2)) The liquid was mixed with 100 ml of water, but did not contain any reactive additive (Laromer® LR-9000). A liquid crystal layer forming composition (B-2) was prepared in the same manner as in the preparation of the liquid crystal layer forming composition (B-1).

[0193] (Preparation of second retardation layer (2) with base layer) On the alignment layer, the liquid crystal layer forming composition (B-2) was applied in place of the liquid crystal layer forming composition (B-1), and the accumulated light amount in the subsequent ultraviolet irradiation was set to 700 mJ / cm 2 Except for this, the second retardation layer with the substrate layer (2) was obtained in the same procedure as in the preparation of the second retardation layer with the substrate layer (1). The thickness of the second liquid crystal layer in the second retardation layer with the substrate layer (2) was 0.8 μm. When the PET film (second substrate layer) was separated from the second retardation layer with the substrate layer (2), the peeling interface was between the alignment layer and the second liquid crystal layer, the thickness of the second retardation layer (second liquid crystal layer) was 0.8 μm, and the puncture modulus E2 of the second retardation layer was 8.2 g / mm.

[0194] (Preparation of the first laminate and the optical laminate) Except that the second retardation layer (2) with a base layer was used instead of the second retardation layer (1) with a base layer A first laminate and an optical laminate were obtained in the same manner as in Comparative Example 1.

[0195] [Example 2 (Optical Laminate 1)] The first laminate and the optical laminate were obtained in the same manner as in Example 1, except that an adhesive layer having the storage modulus shown in Table 1 ("P-3132" manufactured by Lintec Corporation, a sheet-like adhesive having a thickness of 25 μm) was used instead of the adhesive layer used in the preparation of the optical laminate in Example 1.

[0196] [Comparative Example 2 (Comparative Example of Optical Laminate Having First Retardation Layer and Second Retardation Layer)] An optical laminate was obtained in the same manner as in Comparative Example 1, except that an adhesive layer having the storage modulus shown in Table 1 ("P-3132" manufactured by Lintec Corporation, a sheet-like adhesive having a thickness of 25 μm) was used instead of the adhesive layer used in the preparation of the optical laminate in Comparative Example 1.

[0197] [Table 1]

[0198] [Example 3 (Optical Laminate 2)] The second retardation layer (2) with the substrate layer obtained in Example 1 was used as the retardation layer (X) with the substrate layer. The retardation layer (X) with the substrate layer was used to evaluate the separation speed dependency of the peeling force according to the procedure for measuring the peeling force of the retardation layer (X). The results are shown in Table 2.

[0199] The surface of the retardation layer (X) side of the retardation layer (X) with the base layer was subjected to corona treatment (treatment conditions: 800 W, 10 m / min, bar width 700 mm, 1 pass), and the corona-treated surface was bonded to the optical film prepared in Comparative Example 1 via an adhesive layer having a storage modulus shown in Table 2 ("NCF #L2" manufactured by Lintec Corporation, a sheet-like adhesive having a thickness of 5 μm) to obtain an optical laminate.

[0200] [Comparative Example 3 (Optical laminate having retardation layer (X)] An optical laminate was obtained in the same manner as in Example 3, except that the second retardation layer (1) with the base layer obtained in Comparative Example 1 was used.

[0201] [Comparative Example 4 (Optical laminate having retardation layer (X)] The second retardation layer (1) with the base material layer obtained in Comparative Example 1 was used, and an optical laminate was obtained in the same manner as in Example 3, except that an adhesive layer having a storage modulus shown in Table 2 ("P-3132" manufactured by Lintec Corporation, a sheet-like adhesive having a thickness of 25 μm) was used instead of the adhesive layer used in the preparation of the optical laminate in Example 3.

[0202] [Table 2] [Explanation of symbols]

[0203] 1, 1a, 1b, 1c, 1d Optical laminate, 10 First retardation layer, 11 First alignment layer, 12 First liquid crystal layer, 15 First base layer, 18 First retardation layer with base layer, 20 Second retardation layer (retardation layer (X)), 21 Second alignment layer (alignment layer (X)), 22 Second liquid crystal layer (liquid crystal layer (X)), 25 Second base layer (base layer (X)), 28 Second retardation layer with base layer (retardation layer with base layer (X)), 31 Pressure-sensitive adhesive layer, 32 Bonding layer, 40 Optical film, 50 Retardation layer (X), 51 Alignment layer (X), 52 Liquid crystal layer (X), 55 Base layer (X), 61 First laminate, 62 second laminate, 63 third laminate, 64 fourth laminate.

Claims

1. An optical laminate including an optical film, a pressure-sensitive adhesive layer, and a retardation layer-containing layer including a retardation layer (X) in this order, The retardation layer (X) is The retardation layer-containing layer is disposed at a position farthest from the pressure-sensitive adhesive layer, A liquid crystal layer (X) which is a cured layer of a polymerizable liquid crystal compound, and does not include an alignment layer; and The puncture elastic modulus E(X) is 5 g / mm or more and 12 g / mm or less, The retardation layer-containing layer includes a first retardation layer, an attachment layer, and a second retardation layer in this order from the pressure-sensitive adhesive layer side, The first retardation layer includes a first liquid crystal layer which is a cured layer of a polymerizable liquid crystal compound, The second retardation layer is the retardation layer (X), the pressure-sensitive adhesive layer has a storage modulus of 3.0×10 6 N / m 2 or less, measured by a torsional shear method at a temperature of 23° C. and a frequency of 1 Hz; The puncture elastic modulus E(X) is determined based on the stress and strain calculated by piercing the surface of the retardation layer (X) perpendicularly with a needle having a tip diameter of 1 mmφ and 0.5R at a speed of 0.33 cm / sec. An optical laminate.

2. The optical laminate according to claim 1 , wherein the puncture elastic modulus E(X) is 7 g / mm or more and 10 g / mm or less.

3. The optical laminate according to claim 1 , wherein the first retardation layer is a laminate of the first liquid crystal layer and a first alignment layer.

4. The puncture elastic modulus E1 of the first retardation layer is 15 g / mm or less, The puncture elastic modulus E1 is determined based on the stress and strain amount calculated by puncturing the surface of the first retardation layer perpendicularly with a needle having a tip diameter of 1 mmφ and 0.5R at a speed of 0.33 cm / sec. The optical laminate according to any one of claims 1 to 3.

5. The optical laminate according to any one of claims 1 to 4, wherein the attachment layer is a cured adhesive layer.

6. The storage modulus of the pressure-sensitive adhesive layer measured by a torsional shear method at a temperature of 80° C. and a frequency of 1 Hz was 6.0×10 5 N / m 2 The optical laminate according to any one of claims 1 to 5, wherein:

7. The optical laminate according to any one of claims 1 to 6, wherein the optical film comprises a polarizing plate having a linear polarizing layer and a protective layer provided on one or both sides of the linear polarizing layer.

8. The storage modulus of the pressure-sensitive adhesive layer measured by a torsional shear method at a temperature of 23° C. and a frequency of 1 Hz was 1×10 5 N / m 2 The optical laminate according to any one of claims 1 to 7.

9. The storage modulus of the pressure-sensitive adhesive layer measured by a torsional shear method at a temperature of 80° C. and a frequency of 1 Hz was 1×10 4 N / m 2 The optical laminate according to claim 6 .

10. A method for producing an optical laminate including an optical film, a pressure-sensitive adhesive layer, and a retardation layer-containing layer including a retardation layer (X) in this order, A step of preparing a retardation layer (X) with a substrate layer having a substrate layer (X) and the retardation layer (X); A step of preparing a laminate having the optical film, the pressure-sensitive adhesive layer, the retardation layer-containing layer, and the base layer (X) in this order, using the optical film, the pressure-sensitive adhesive layer, and the base layer-attached retardation layer (X); and peeling the base layer (X) from the laminate, The retardation layer (X) is The retardation layer-containing layer is disposed at a position farthest from the pressure-sensitive adhesive layer, A liquid crystal layer (X) formed by polymerizing a polymerizable liquid crystal compound on the base layer (X), which does not include an alignment layer, and The puncture elastic modulus E(X) is 5 g / mm or more and 12 g / mm or less, The retardation layer-containing layer includes a first retardation layer, an attachment layer, and a second retardation layer in this order from the pressure-sensitive adhesive layer side, The first retardation layer includes a first liquid crystal layer formed by polymerizing a polymerizable liquid crystal compound on a first base layer, The second retardation layer is the retardation layer (X), the pressure-sensitive adhesive layer has a storage modulus of 3.0×10 6 N / m 2 or less, measured by a torsional shear method at a temperature of 23° C. and a frequency of 1 Hz; The puncture elastic modulus E(X) is determined based on the stress and strain amount calculated by puncturing the surface of the retardation layer (X) perpendicularly with a needle having a tip diameter of 1 mmφ and 0.5R at a speed of 0.33 cm / sec. A method for producing an optical laminate.

11. The method for producing an optical laminate according to claim 10, wherein the puncture elastic modulus E(X) is 7 g / mm or more and 10 g / mm or less.

12. The step of preparing the laminate includes: A step of preparing a first retardation layer with a base material layer having the first base material layer and the first retardation layer; A step of bonding the first retardation layer side of the first retardation layer with the base layer and the retardation layer (X) side of the retardation layer with the base layer (X) via the bonding layer; A step of separating the first base material layer after the step of bonding via the bonding layer; The method for producing an optical laminate according to claim 10 or 11, further comprising: a step of bonding an exposed surface exposed by separating the first base layer and the optical film via the pressure-sensitive adhesive layer.

13. The step of preparing the laminate includes: A step of preparing a first retardation layer with a base material layer having the first base material layer and the first retardation layer; a step of bonding the optical film and the first retardation layer side of the base layer-attached first retardation layer via a pressure-sensitive adhesive layer; a step of separating the first base layer after the step of bonding via the pressure-sensitive adhesive layer; The method for producing an optical laminate according to claim 10 or 11, further comprising: a step of bonding an exposed surface exposed by separating the first base material layer and the retardation layer (X) side of the base material layer-attached retardation layer (X) via the bonding layer.

14. The puncture elastic modulus E1 of the first retardation layer is 15 g / mm or less, The puncture elastic modulus E1 is determined based on the stress and strain amount calculated by puncturing the surface of the first retardation layer perpendicularly with a needle having a tip diameter of 1 mmφ and 0.5R at a speed of 0.33 cm / sec. The method for producing an optical laminate according to claim 13.

15. The method for producing an optical laminate according to any one of claims 10 to 14, wherein the first retardation layer with a base layer has a first alignment layer between the first base layer and the first liquid crystal layer.

16. The storage modulus of the pressure-sensitive adhesive layer measured by a torsional shear method at a temperature of 80° C. and a frequency of 1 Hz was 6.0×10 5 N / m 2 The method for producing an optical laminate according to any one of claims 10 to 15, wherein:

Citation Information

Patent Citations

  • Optical laminate

    CN110579830A

  • Transfer body for optical film, optical film, and method for manufacturing transfer body for optical film

    JP2015040953A

  • Method for manufacturing circularly polarizing plate

    JP2015187717A

  • Optical laminate in a long form and image display device

    JP2017102286A

  • Polarizing plate and liquid crystal panel

    JP2017102426A